Laminate and method for producing laminate

By using the hydrogenation coaxyne composite cluster in the adhesive layer of the layers as a adhesive, the problem of lack of adhesion strength without using organic solvents without using organic solvents is solved, and the appearance is good. The effect of high adhesion intensity.

CN119343241APending Publication Date: 2025-01-21ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380044065.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-07
Filing Date
2023-04-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, the laminate has insufficient bonding strength without using an organic solvent, making it difficult to meet the needs of good appearance and high bonding strength.

Method used

By using a hydrogenation co -dizide system with a specific structure in the adhesive layer of the layer, a polymer, or mixing the hydrogenated co -segment co -vector in the polyolefin resin layer , To improve adhesion intensity.

Benefits of technology

With the case without using organic solvents, it forms a well -existent appearance and high adhesion strength, which solves the problem of insufficient adhesion intensity in existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161665520000321
    Figure BDA0005161665520000321
  • Figure BDA0005161665520000491
    Figure BDA0005161665520000491
  • Figure BDA0005161665520000511
    Figure BDA0005161665520000511
Patent Text Reader

Abstract

The present invention provides a laminate having a layer (I) mainly composed of an acrylic resin, a layer (II) mainly composed of a polyolefin resin, and an adhesive layer (III) provided between the layer mainly composed of the acrylic resin and the layer mainly composed of the polyolefin resin, the adhesive layer (III) is composed of an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer. Hydrogenated conjugated diene block copolymer having polymer block (A) mainly composed of vinyl aromatic monomer unit, polymer block (B) mainly composed of conjugated diene monomer unit, and polymer block (C) having vinyl aromatic monomer unit and conjugated diene monomer unit two or more types of polymer blocks in the formed group, wherein unsaturated bonds of conjugated diene monomer units are hydrogenated; the hydrogenated conjugated diene block copolymer satisfies predetermined conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate and a method for producing the laminate. Background Art

[0002] Conventionally, as a molded body having excellent appearance, transparency and decorativeness, a laminate having a base composed of a polyolefin resin such as a polypropylene resin and an acrylic resin layer having excellent appearance has been proposed for moldability and low cost.

[0003] For example, Patent Document 1 proposes a laminate composed of a substrate having a polypropylene-based resin and a thermoplastic resin as main components, a sealant layer, and an acrylic resin layer.

[0004] On the other hand, polyolefin resins and acrylic resins have the problem of being difficult to bond together from the viewpoint of solubility parameters, etc. In order to solve this problem, laminates using solvent-based adhesives such as acrylic adhesives and urethane adhesives as adhesives have been proposed.

[0005] However, from the perspective of reducing VOC (volatile organic compounds), there is an increasing demand for a laminate molding method technology that does not use an organic solvent.

[0006] For example, Patent Document 2 proposes a laminate of a substrate composed of a polypropylene resin and an acrylic resin layer, wherein an adhesive layer containing a polypropylene resin as a non-solvent adhesive is provided on a substrate composed of a polypropylene resin.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-181232

[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-14027 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the laminate disclosed in Patent Document 2 still has a problem that there is room for improvement in terms of adhesive strength.

[0013] Therefore, an object of the present invention is to provide a laminate having a good appearance and high adhesive strength without using an organic solvent.

[0014] Means for solving problems

[0015] The present inventors have conducted intensive studies to solve the problems of the above-mentioned prior art and have found that, in order to bond a layer mainly composed of a polyolefin resin to a layer mainly composed of an acrylic resin, by providing an adhesive layer mainly composed of a hydrogenated conjugated diene block copolymer having a specific structure, or by mixing a hydrogenated conjugated diene block copolymer as an adhesive component into a layer mainly composed of a polyolefin resin, a laminate having a good appearance and high bonding strength can be formed without using an organic solvent, thereby completing the present invention.

[0016] That is, the present invention is as follows. [1]

[0018] A laminate comprising:

[0019] A layer (I) mainly composed of acrylic resin;

[0020] a layer (II) mainly composed of a polyolefin resin; and

[0021] The adhesive layer (III) provided between the layer mainly composed of acrylic resin and the layer mainly composed of polyolefin resin is:

[0022] The adhesive layer (III) is composed of an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit, wherein the unsaturated bonds of the conjugated diene monomer unit are hydrogenated.

[0023] The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv).

[0024] <Condition (i)>

[0025] The hydrogenated conjugated diene block copolymer has a polar group.

[0026] <Condition (ii)>

[0027] The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises units (a) derived from 1,2-bonds and / or 3,4-bonds of a conjugated diene compound and units (b) derived from 1,4-bonds, and when the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 50% or more.

[0028] <Condition (iii)>

[0029] The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C).

[0030] <Condition (iv)>

[0031] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less. [2]

[0033] The laminate as described in the above [1], wherein the hydrogenated conjugated diene block copolymer satisfies the above conditions (i), (iii), and (iv). [3]

[0035] The laminate as described in the above [1], wherein the hydrogenated conjugated diene block copolymer satisfies the above conditions (ii), (iii), and (iv). [4]

[0037] The laminate as described in the above [1], wherein the hydrogenated conjugated diene block copolymer satisfies the above conditions (i) and (ii), does not satisfy the above condition (iv), and further satisfies the following condition (v).

[0038] <Condition(v)>

[0039] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is less than 25% by mass. [5]

[0041] A laminate as described in any one of [1] to [4] above, wherein the hydrogenated conjugated diene block copolymer satisfies the condition (i), and the polar group possessed by the hydrogenated conjugated diene block copolymer is at least one selected from the group consisting of anhydride group, amino group, dicarboxyl group, carboxyl group, epoxy group and oxetane group. [6]

[0043] The laminate as described in the above [5], wherein the polar group contained in the hydrogenated conjugated diene block copolymer is an amino group. [7]

[0045] The laminate according to any one of the above-mentioned [1] to [6], wherein the hydrogenation rate of the hydrogenated conjugated diene block copolymer is 90% or less. [8]

[0047] The laminate according to any one of [1] to [7], wherein the thickness of the layer (I) mainly composed of an acrylic resin is 1.5 mm or less. [9]

[0049] The laminate according to any one of [1] to [3] and [5] to [8], wherein the hydrogenated conjugated diene block copolymer satisfies the condition (iv).

[10]

[0051] A method for producing a laminate is the method for producing a laminate according to [1], comprising the following steps:

[0052] A step of laminating the above-mentioned layer (I) mainly composed of acrylic resin and the above-mentioned adhesive layer (III) in such a manner that they are in contact with each other; and

[0053] A step of laminating the layer (II) mainly composed of a polyolefin resin so that the adhesive layer (III) is in contact with the layer (II) mainly composed of a polyolefin resin.

[11]

[0055] The method for producing a laminate as described in the above

[10] , wherein the thickness of the layer (I) mainly composed of acrylic resin is 1.5 mm or less.

[12]

[0057] A method for producing a laminate as described in

[10] or

[11] above, wherein, in the step of laminating the layer (I) mainly composed of an acrylic resin and the adhesive layer (III), the layer (I) mainly composed of an acrylic resin and the adhesive layer (III) are laminated in a molten state.

[13]

[0059] The method for producing a laminate according to any one of

[10] to

[12] , wherein:

[0060] In the step of laminating the above-mentioned layer (II) mainly composed of a polyolefin resin,

[0061] The laminate having the layer (I) mainly composed of the acrylic resin and the adhesive layer (III) is installed in a mold.

[0062] The polyolefin resin is poured into the above-mentioned mold in a molten state.

[14]

[0064] A laminate comprising:

[0065] a layer (I) mainly composed of an acrylic resin; and

[0066] A layer (IV) comprising a polyolefin resin and an adhesive component, wherein

[0067] The amounts of the polyolefin resin and the adhesive component are in a mass ratio of polyolefin resin / adhesive component = 30 / 70 to 95 / 5.

[0068] The adhesive component is an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit, wherein the unsaturated bonds of the conjugated diene monomer unit are hydrogenated,

[0069] The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv).

[0070] <Condition (i)>

[0071] The hydrogenated conjugated diene block copolymer has a polar group.

[0072] <Condition (ii)>

[0073] The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises units (a) derived from 1,2-bonds and / or 3,4-bonds of a conjugated diene compound and units (b) derived from 1,4-bonds, and when the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 50% or more.

[0074] <Condition (iii)>

[0075] The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C).

[0076] <Condition (iv)>

[0077] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less.

[15]

[0079] The laminate according to the above

[14] , wherein the hydrogenated conjugated diene block copolymer satisfies the above conditions (i), (iii), and (iv).

[16]

[0081] The laminate according to the above

[14] , wherein the hydrogenated conjugated diene block copolymer satisfies the above conditions (ii), (iii), and (iv).

[17]

[0083] The laminate according to the above

[14] , wherein the hydrogenated conjugated diene block copolymer satisfies the above conditions (i) and (ii), does not satisfy the above condition (iv), and further satisfies the following condition (v).

[0084] <Condition(v)>

[0085] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is less than 25% by mass.

[18]

[0087] The laminate as described in

[14] or

[15] above, wherein the hydrogenated conjugated diene block copolymer satisfies the above condition (i), and the polar group possessed by the hydrogenated conjugated diene block copolymer is at least one selected from the group consisting of anhydride group, amino group, dicarboxyl group, carboxyl group, epoxy group and oxetane group.

[0088] Effects of the Invention

[0089] According to the present invention, a laminate having a good appearance and high adhesive strength can be provided without using an organic solvent. DETAILED DESCRIPTION

[0090] A specific embodiment of the present invention (hereinafter referred to as “this embodiment”) will be described in detail below.

[0091] It should be noted that the following embodiments are examples for explaining the present invention and are not intended to limit the present invention to the following contents. The present invention can be implemented by appropriately modifying the present invention within the scope of the gist thereof.

[0092] [laminated body]

[0093] The laminate of the present embodiment has the following two forms: a laminate of the first embodiment and a laminate of the second embodiment.

[0094] The laminate of the first embodiment is a laminate having the following layers:

[0095] A layer (I) mainly composed of an acrylic resin (hereinafter sometimes referred to as layer (I));

[0096] a layer (II) mainly composed of a polyolefin resin (hereinafter sometimes referred to as layer (II)); and

[0097] The adhesive layer (III) (hereinafter sometimes referred to as layer (III)) is provided between the layer mainly composed of acrylic resin and the layer mainly composed of polyolefin resin.

[0098] The adhesive layer (III) is composed of an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit, wherein the unsaturated bonds of the conjugated diene monomer unit are hydrogenated.

[0099] The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv).

[0100] <Condition (i)>

[0101] The hydrogenated conjugated diene block copolymer has a polar group.

[0102] <Condition (ii)>

[0103] The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises units (a) derived from 1,2-bonds and / or 3,4-bonds of a conjugated diene compound and units (b) derived from 1,4-bonds, and when the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 50% or more.

[0104] <Condition (iii)>

[0105] The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C).

[0106] <Condition (iv)>

[0107] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less.

[0108] The laminate of the first embodiment has the adhesive layer (III) composed of an adhesive component as a single layer, whereby the stress during impact can be dispersed by the highly flexible hydrogenated conjugated diene block copolymer, and the laminate as a whole exhibits high impact resistance.

[0109] The laminate of the second embodiment is a laminate having the following layers:

[0110] a layer (I) mainly composed of an acrylic resin; and

[0111] A layer (IV) comprising a polyolefin resin and an adhesive component (hereinafter sometimes referred to as layer (IV)).

[0112] The amounts of the polyolefin resin and the adhesive component are in a mass ratio of polyolefin resin / adhesive component = 30 / 70 to 95 / 5.

[0113] The adhesive component is an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit, wherein the unsaturated bonds of the conjugated diene monomer unit are hydrogenated,

[0114] The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv).

[0115] <Condition (i)>

[0116] The hydrogenated conjugated diene block copolymer has a polar group.

[0117] <Condition (ii)>

[0118] The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises units (a) derived from 1,2-bonds and / or 3,4-bonds of a conjugated diene compound and units (b) derived from 1,4-bonds, and when the total content of the conjugated diene monomer units is 100%, the content of the units (a) derived from 1,2-bonds and / or 3,4-bonds is 50% or more.

[0119] <Condition (iii)>

[0120] The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C).

[0121] <Condition (iv)>

[0122] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less.

[0123] The laminate of the second embodiment includes a layer (I) mainly composed of an acrylic resin and a layer (IV) containing a polyolefin resin and an adhesive component.

[0124] The layer (IV) is a form in which the layer (II) mainly composed of a polyolefin resin constituting the laminate of the first embodiment described above contains an adhesive component.

[0125] According to the laminate of the second embodiment, mixing of the adhesive component into the layer (I) mainly composed of an acrylic resin can be suppressed, and the appearance becomes good.

[0126] The laminate of the first embodiment and the laminate of the second embodiment are common in that they have a layer (I) mainly composed of an acrylic resin and a layer mainly composed of a polyolefin resin; and that the main component of the adhesive component is a specific hydrogenated conjugated diene block copolymer.

[0127] The laminated body according to the first embodiment has an independent adhesive layer (III).

[0128] On the other hand, the laminated body according to the second embodiment has a layer (IV) containing an adhesive component and a polyolefin resin.

[0129] The laminate of the first embodiment has excellent impact resistance, but on the other hand, the hydrogenated conjugated diene block copolymer of the adhesive layer (III) and the layer (I) mainly composed of acrylic resin are slightly melted during the molding of the laminate, and thus the appearance tends to be inferior to that of the laminate of the second embodiment. Therefore, it is preferable to select the form according to whether the application requires impact resistance or the application requires good appearance.

[0130] (Layer(I))

[0131] The laminated bodies of the first and second embodiments include a layer (I) mainly composed of an acrylic resin.

[0132] By using an acrylic resin as the main component, a laminate having excellent appearance can be obtained.

[0133] Here, "mainly composed of acrylic resin" means that the acrylic resin accounts for 30% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more in 100% by mass of the entire layer (I).

[0134] Examples of the acrylic resin include, but are not limited to, acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, methyl methacrylate-butyl methacrylate copolymer, and methyl methacrylate-styrene copolymer. In addition, as the acrylic resin, a mixed resin of the above acrylic resin and a thermoplastic polyurethane resin, a mixed resin of the above acrylic resin and an acrylic rubber, and the like can be used.

[0135] In the layer (I) mainly composed of acrylic resin, as components other than acrylic resin, common additives such as stabilizers, lubricants, processing aids, impact-resistant aids, fillers, colorants, matting agents, ultraviolet absorbers, etc. may be contained as needed. In this case, the content of acrylic resin in layer (I) is converted as the whole mixed material.

[0136] Examples of commercially available products of the acrylic resin include ACRYPET (manufactured by Mitsubishi Rayon Co., Ltd.), SUMIPEX (manufactured by Sumitomo Chemical Co., Ltd.), and DELPET (manufactured by Asahi Kasei Corporation).

[0137] (Layer (II))

[0138] The laminated body according to the first embodiment has a layer (II) mainly composed of a polyolefin resin.

[0139] The layer (II) mainly composed of a polyolefin resin mainly contains a polyolefin resin other than the hydrogenated conjugated diene block copolymer described later.

[0140] Here, "mainly composed of a polyolefin resin" means that the polyolefin resin accounts for 30 mass% or more, preferably 40 mass% or more, more preferably 50 mass% or more, and even more preferably 60 mass% or more in 100 mass% of the entire layer (II).

[0141] The layer (II) of the laminate of the first embodiment does not contain an adhesive component described below.

[0142] (Layer (IV))

[0143] The laminate according to the second embodiment includes a layer (IV) containing a polyolefin resin and an adhesive component.

[0144] Layer (IV) contains a polyolefin resin other than the hydrogenated conjugated diene block copolymer described below and an adhesive component described below. In layer (IV), the amount of the polyolefin resin and the adhesive component is polyolefin resin / adhesive component = 30 / 70 to 95 / 5 in terms of mass ratio.

[0145] The preferred form of the polyolefin resin is common to both layer (II) and layer (IV).

[0146] <Polyolefin resin>

[0147] Examples of the polyolefin resin used in the layer (II) and the layer (IV) include, but are not limited to, polyethylene resins and polypropylene resins.

[0148] Examples of the polyethylene resin include low-density polyethylene, linear low-density polyethylene, high-density polyethylene, and copolymers of ethylene and α-olefins having 3 to 8 carbon atoms. When the polyethylene resin is a copolymer of ethylene and α-olefins having 3 to 8 carbon atoms, examples of the α-olefin in the copolymer include propylene, 1-butene, isobutylene, 1-pentene, 1-hexene, 4-methyl-1-pentene, and 1-octene.

[0149] Examples of the polypropylene resin include propylene homopolymers synthesized using a Ziegler-Natta catalyst, and random or block copolymers of propylene and α-olefins. In the case of a copolymer of propylene and α-olefins, the proportion of the α-olefin relative to 100% by mass of the polypropylene resin is preferably 30% by mass or less, more preferably 35% by mass or less.

[0150] Specifically, the polypropylene resin includes a propylene homopolymer and a copolymer of propylene and an α-olefin having 2 to 8 carbon atoms (hereinafter also referred to as a "propylene-based resin"). When the polypropylene resin is a copolymer of propylene and an α-olefin having 2 to 8 carbon atoms, examples of the α-olefin in the copolymer include ethylene, 1-butene, isobutylene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, and the like.

[0151] These polyolefin resins can be synthesized by conventionally known methods.

[0152] From the viewpoint of heat resistance (heat aging resistance) and moldability, the polyolefin resin is preferably a polypropylene resin.

[0153] The MFR (melt flow rate) of the polyolefin resin used in layer (II) and layer (IV) is usually 1.0 to 1000 g / 10 minutes, preferably 5.0 to 100 g / 10 minutes. By making the MFR of the polyolefin resin 1.0 g / 10 minutes or more, there is a tendency to improve the molding processability (fluidity) of layer (II) and layer (IV). In addition, there is a tendency to suppress the deterioration of the appearance of the molded product (the occurrence of flow marks).

[0154] The polyolefin resins used in the layer (II) and the layer (IV) may be used alone or in combination of two or more.

[0155] In addition, from the perspective of improving the impact resistance of the layer and adjusting the hardness and fluidity, layer (II) and layer (IV) may also contain an olefin-based elastomer. Olefin-based elastomers are, for example, copolymers of ethylene and / or propylene and α-olefins having 3 to 8 carbon atoms, as mentioned above as the polyolefin resin, and the proportion of α-olefins is above the above-mentioned preferred proportions. Specifically, relative to 100% by mass of the entire olefin-based elastomer, the proportion of α-olefins is 30% by mass or more, preferably greater than 30% by mass, further preferably 35% by mass or more, and more preferably 40% by mass or more. By making the proportion of α-olefins within the above-mentioned range, the olefin-based elastomer has low rigidity and tends to be able to improve the impact resistance of the laminate of the present embodiment.

[0156] (Adhesive layer (III))

[0157] The laminate of the first embodiment has an adhesive layer (III) composed of an adhesive component between the above-mentioned layer (I) and layer (II).

[0158] (Layer (IV) comprising polyolefin resin and adhesive component)

[0159] The laminate according to the second embodiment includes a layer (IV) containing the above-mentioned polyolefin resin and an adhesive component.

[0160] In the laminate of the first embodiment, the adhesive layer (III) is an independent layer composed of an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer described later.

[0161] Here, "mainly composed of hydrogenated conjugated diene block copolymer" means that the content of the hydrogenated conjugated diene block copolymer in the adhesive component is 50% by mass or more, and other components may be included within a range that does not impair the appearance and bonding strength. From the aspects of the bonding strength and appearance, the content of the hydrogenated conjugated diene block copolymer in the adhesive component is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, further more preferably 90% by mass or more, and further preferably 95% by mass or more.

[0162] In the laminate of the second embodiment, the layer (IV) contains the above-mentioned polyolefin resin and an adhesive component described later.

[0163] The mass ratio of the polyolefin resin to the adhesive component is polyolefin resin / adhesive component = 30 / 70 to 95 / 5, preferably 35 / 65 to 95 / 5, more preferably 40 / 60 to 95 / 5, further preferably 45 / 55 to 95 / 5, further more preferably 50 / 50 to 95 / 5, further more preferably 60 / 40 to 90 / 10.

[0164] In addition, the content of the hydrogenated conjugated diene block copolymer in the adhesive component is the same as that in the above-mentioned adhesive layer (III).

[0165] <Adhesive ingredients>

[0166] In any of the first and second embodiments, the adhesive component is composed of an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, and the unsaturated bonds of the conjugated diene monomer unit are hydrogenated. The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv).

[0167] The structures of the polymer block (A), the polymer block (B), and the polymer block (C) are as follows.

[0168] Condition (i):

[0169] The hydrogenated conjugated diene block copolymer has a polar group.

[0170] Condition (ii):

[0171] The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises units derived from 1,2-bonds and / or 3,4-bonds of a conjugated diene compound (hereinafter also referred to as "unit (a)") and units derived from 1,4-bonds (hereinafter also referred to as "unit (b)"), and when the content of the conjugated diene monomer unit is 100%, the content of the unit (a) is 50% or more (vinyl bond content).

[0172] Condition (iii):

[0173] The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C).

[0174] Condition (iv):

[0175] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less.

[0176] The adhesive component has high compatibility with acrylic resin and polyolefin resin, so that the laminate of the present embodiment shows high bonding strength. Although it can be simply considered that the adhesive component contains a hydrogenated conjugated diene block copolymer whose solubility parameter (sp value) is close to that of the two resins, the solubility parameter (sp value) of acrylic resin is higher than that of polyolefin resin. In order to bond the layer (I) and layer (II) with resins having different solubility parameters as the main body, the hydrogenated conjugated diene block copolymer contained in the adhesive component is required to have a polymer skeleton compatible with the two resins.

[0177] In order to improve the compatibility with the acrylic resin, the hydrogenated conjugated diene block copolymer preferably satisfies the above-mentioned conditions (i) and / or (iii) and / or (iv) from the viewpoint of the solubility parameter (sp value).

[0178] In order to improve the compatibility with the polyolefin resin, the hydrogenated conjugated diene block copolymer preferably satisfies the condition (ii) and / or the condition (iii) and / or the condition (iv).

[0179] Therefore, by satisfying two or more of the above conditions (i) to (iv), the hydrogenated conjugated diene block copolymer has high compatibility with layer (I) and layer (II), and particularly has excellent compatibility with polyolefin resins from the viewpoint of solubility parameters.

[0180] Therefore, in either the case of a structure having an adhesive layer (III) (which is a separate layer of an adhesive component) or a structure having a layer (IV) containing a polyolefin resin and an adhesive component, a laminate having high bonding strength can be obtained without impairing the appearance of the layer (I) mainly composed of an acrylic resin.

[0181] The adhesive component may contain other adhesive components other than the hydrogenated conjugated diene block copolymer within a range that does not impair the appearance and the adhesive strength.

[0182] By providing the hydrogenated conjugated diene block copolymer used in the adhesive component with a polar group as in the above condition (i), the sp value of the hydrogenated conjugated diene block copolymer can be increased, thereby improving the compatibility and reactivity of the acrylic resin in layer (I) and the hydrogenated conjugated diene block copolymer.

[0183] It is known that the sp value of vinyl aromatic compounds is higher than that of conjugated diene compounds. Therefore, by making the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer be 25 mass % or more and 80 mass % or less as in the above condition (iv), the hydrogenated conjugated diene block copolymer has excellent compatibility with each of layer (I) and layer (II).

[0184] When the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more, the sp value of the hydrogenated conjugated diene block copolymer can be sufficiently increased, thereby improving the compatibility with the layer (I) mainly composed of an acrylic resin and obtaining sufficient adhesive strength.

[0185] By setting the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer to 80% by mass or less, it is possible to suppress the sp value from becoming too high, improve the compatibility with the layer (II) mainly composed of a polyolefin resin, and obtain sufficient adhesive strength.

[0186] In the above condition (iv), the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is preferably 30 to 75% by mass, more preferably 35 to 70% by mass, further preferably 40 to 70% by mass, further more preferably 45 to 70% by mass, further preferably 50 to 70% by mass, and particularly preferably 55 to 70% by mass.

[0187] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer can be controlled within the above numerical range by adjusting the amount of the vinyl aromatic compound added and the polymerization time in the polymerization step.

[0188] In addition, from the aspect of obtaining sufficient bonding strength, it is preferred that the hydrogenated conjugated diene block copolymer has at least one polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit as in the above condition (iii). Thus, the hydrogenated conjugated diene block copolymer has excellent compatibility with each of the layer (I) and the layer (II), and the bonding strength is improved.

[0189] In addition, it is known that the compatibility of the above-mentioned unit (a) (hereinafter sometimes described as vinyl bond) with polyolefin resin is better than that of the above-mentioned unit (b). Therefore, by making the vinyl bond content of the above-mentioned hydrogenated conjugated diene block copolymer 50% or more, the compatibility with the polyolefin resin of layer (II) is improved and the bonding strength is improved.

[0190] The amount of vinyl bonds in the hydrogenated conjugated diene block copolymer before hydrogenation is preferably 55% or more, more preferably 60% or more, further preferably 65% ​​or more, further more preferably 67% or more, and further preferably 70% or more.

[0191] The vinyl bond content can be measured by the method described in the examples below, and can be controlled within the above numerical range by using a vinyl bond content adjuster (vinylating agent) as described below.

[0192] In the hydrogenated conjugated diene block copolymer in the adhesive component, the unsaturated bonds derived from the conjugated diene compound are hydrogenated.

[0193] By hydrogenating the conjugated diene monomer units having excellent compatibility with the polyolefin resin in layer (II), the difference in sp value between the polymer blocks (B) and (C) of the hydrogenated conjugated diene block polymer and the polyolefin resin is further reduced, thereby improving the compatibility of the hydrogenated conjugated diene block copolymer with layer (II).

[0194] Furthermore, since the number of thermally unstable unsaturated bonds decreases due to hydrogenation, heat aging resistance, weather resistance, and mold contamination resistance (property for preventing mold contamination) tend to be improved.

[0195] From the above viewpoints, the hydrogenation rate (hydrogenation rate) is preferably 80% or more, more preferably 83% or more, and even more preferably 85% or more.

[0196] Furthermore, as described below, from the viewpoint of heat cycle resistance and hot water resistance of the laminate of the present embodiment, the hydrogenation rate of the hydrogenated conjugated diene block copolymer is preferably 90% or less. This is described below.

[0197] The hydrogenation rate of the hydrogenated conjugated diene block copolymer can be measured using a nuclear magnetic resonance apparatus (NMR) or the like, and specifically, can be measured by the method described in Examples.

[0198] In addition, the hydrogenation rate can be controlled within the above numerical range by adjusting the amount of hydrogen reacting during the hydrogenation reaction, for example.

[0199] By making the tanδ peak temperature in the viscoelasticity measurement of the adhesive component at the use environment temperature of the laminate of the present embodiment, there is a tendency that a laminate with excellent vibration damping and quietness can be obtained. By making the hydrogenated conjugated diene block copolymer contained in the adhesive component satisfy the above conditions (iii) and (iv), there is a tendency that the tanδ peak temperature of the hydrogenated conjugated diene block copolymer is above 0°C. In addition, by satisfying the above condition (i), there is a tendency that high bonding strength can be exhibited, which also contributes to improving vibration damping.

[0200] From the above aspects, when the hydrogenated conjugated diene block copolymer satisfies the above conditions (i), (iii) and (iv), a laminate having excellent vibration damping properties, adhesive strength and impact resistance at room temperature and good appearance tends to be obtained.

[0201] When the hydrogenated conjugated diene block copolymer used in the adhesive component satisfies the above condition (i), decomposition products derived from the modifier used to bond polar groups to the hydrogenated conjugated diene block copolymer tend to volatilize during molding, causing mold contamination or deteriorating the working environment.

[0202] When the hydrogenated conjugated diene block copolymer satisfies the above condition (i), from the perspective of suppressing the decomposition products from the modifier, making the molding cycle and the working environment good, the amount of the unreacted modifier is preferably small, and the amount of the unreacted modifier is preferably 0.2% by mass or less, more preferably 0.15% by mass or less, further preferably 0.1% by mass or less, and further more preferably 0.05% by mass or less relative to the hydrogenated conjugated diene block copolymer after the modification process. Similarly, from the perspective of suppressing mold contamination, the reaction rate of the hydrogenated conjugated diene block copolymer and the modifier described later is preferably high.

[0203] As a method for bonding a polar group to the hydrogenated conjugated diene block copolymer, the following methods can be cited as preferred methods: a method of introducing by using a polymerization initiator having predetermined functional groups that become polar groups as described later, a method of polymerizing unsaturated monomers having various functional groups, a method of forming a functional group at an active terminal, and a method of subjecting a modifier having a functional group to an addition reaction.

[0204] As the polar group, for example, anhydride group, amino group, dicarboxyl group, carboxyl group, epoxy group and oxetanyl group can be cited but are not limited thereto. From the aspect of the above reaction rate, amino group and epoxy group are preferred, and from the aspect of being easy to set in a manner to reduce the amount of unreacted modifier by controlling the amount added, amino group is more preferred.

[0205] On the other hand, when the hydrogenated conjugated diene block copolymer satisfies conditions (ii), (iii) and (iv), the hydrogenated conjugated diene block copolymer is less likely to decompose and the volatilization of the decomposition product is small, so there is a tendency to ensure excellent molding cycle performance and working environment properties.

[0206] When the use temperature of the laminate of this embodiment is low temperature (below 0°C), it is preferable to use a highly flexible adhesive component. By making the adhesive component highly flexible, stress can be dispersed even at low temperatures, and there is a tendency for the laminate of this embodiment to exhibit high impact resistance.

[0207] From the above aspects, by making the hydrogenated conjugated diene block copolymer satisfy conditions (i), (ii) and the following condition (v), the refractive indexes of the acrylic resin and the hydrogenated conjugated diene block copolymer are easily close, which tends to easily improve the transparency of the laminate in this embodiment, and there is a tendency to obtain a laminate with excellent impact resistance and bonding strength at low temperatures.

[0208] Condition (v): The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is less than 25% by mass.

[0209] In the above condition (v), the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is preferably 20 mass % or less, more preferably 17 mass % or less, further preferably 15 mass % or less, and still more preferably 13 mass % or less.

[0210] The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer can be controlled within the above numerical range by adjusting the amount of the vinyl aromatic compound added and the polymerization time in the polymerization step.

[0211] When the hydrogenated conjugated diene block copolymer used in the adhesive component satisfies the above-mentioned condition (i), from the aspect of compatibility with the above-mentioned layer (I) mainly composed of an acrylic resin, as described above, the polar group is preferably at least one selected from the group consisting of an acid anhydride group, an amino group, a dicarboxyl group, a carboxyl group, an epoxy group and an oxetane group, and more preferably at least one selected from the group consisting of an acid anhydride group, an amino group, a dicarboxyl group and a carboxyl group.

[0212] By making the hydrogenated conjugated diene block copolymer have at least one polar group selected from the above group, the hydrogenated conjugated diene block copolymer has affinity and / or reactivity with the acrylic resin, and has a tendency to obtain a laminate with high bonding strength. Affinity refers to the generation of at least one intermolecular force selected from the group consisting of ionic interaction, hydrogen bonding, dipole interaction, and van der Waals force between the components. Reactivity refers to the covalent bonding between the polar groups of the components. When a reaction occurs between the polar groups, for example, when the OH of the carboxyl group is detached, the original polar group changes or disappears, but in the case of forming a covalent bond, it is included in the definition of "reactivity" between the polar groups.

[0213] From the viewpoint of adhesiveness, it is preferred that the hydrogenated conjugated diene block copolymer has affinity and reactivity. From the viewpoint of reactivity, it is preferred that the polar group possessed by the hydrogenated conjugated diene block copolymer is an amino group.

[0214] The amount of polar groups in the hydrogenated conjugated diene block copolymer is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.10% by mass or more, relative to the entire hydrogenated conjugated diene block copolymer from the perspective of compatibility with the layer (I) mainly composed of an acrylic resin.

[0215] From the viewpoints of the mold contamination and the working environment, the amount of polar groups in the hydrogenated conjugated diene block copolymer is preferably 20% by mass or less.

[0216] The amount of polar groups in the hydrogenated conjugated diene block copolymer can be controlled within the above numerical range by adjusting the reaction conditions with the compounds for forming these polar groups, such as the amount of compound added, reaction temperature, reaction time, etc., during the production process of the hydrogenated conjugated diene block copolymer.

[0217] In recent years, when decorative laminates are used as materials for automobile interior and exterior, etc., there is a tendency to require high adhesion (heat cycle resistance, hot water resistance) in the above-mentioned decorative laminates not only at room temperature but also in a wide temperature range or in a high temperature and high humidity environment.

[0218] In order to achieve sufficient heat cycle resistance and hot water resistance, the adhesive component used in the layer (III) preferably has a polar group reactive with the acrylic resin.

[0219] In order to make the laminate of this embodiment have sufficient heat cycle resistance and / or hot water resistance when the thickness of layer (I) is thin, the hydrogenated conjugated diene block copolymer is required to have high compatibility with the acrylic resin not only near the interface between layer (I) and layer (III) but also near the outer layer. However, if the hydrogenated conjugated diene block copolymer is compatible with the acrylic resin near the outer layer, the appearance will not be impaired and the adhesion with layer (II) tends to be reduced.

[0220] In view of such problems, from the viewpoint of obtaining sufficient heat cycle resistance and / or hot water resistance, the polar group possessed by the hydrogenated conjugated diene-based copolymer is preferably an amino group from the viewpoint of exhibiting reactivity with the acrylic resin.

[0221] In addition, from the perspective of increasing the covalent bonding between the acrylic resin of the above-mentioned layer (I) and the hydrogenated conjugated diene block copolymer of the layer (III) and improving the heat cycle resistance and hot water resistance of the laminate of this embodiment, the hydrogenation rate of the hydrogenated conjugated diene block copolymer is preferably 90% or less, more preferably 88% or less, further preferably 86% or less, and further preferably 85% or less.

[0222] Acrylic resins generally have unsaturated bonds that are free radical reactive due to side reactions during polymerization. When the hydrogenation rate of the hydrogenated conjugated diene block copolymer is 90% or less, the unsaturated bonds from the conjugated dienes that are not hydrogenated and remain in the hydrogenated conjugated diene block copolymer react with the unsaturated bonds of the acrylic resin during the manufacture of the laminate to form covalent bonds, thereby tending to improve the heat cycle resistance and hot water resistance of the laminate of this embodiment.

[0223] On the other hand, from the viewpoint of preventing gelation and suppressing mold contamination, it is preferred that unsaturated bonds in the hydrogenated conjugated diene block copolymer do not remain excessively.

[0224] In addition, if the amount of unreacted modifier is reduced, mold contamination tends to be suppressed.

[0225] From the perspective of the heat aging resistance, weather resistance, and suppression of the appearance reduction of the laminate of the present embodiment due to crosslinking between hydrogenated conjugated diene block copolymers and suppression of mold contamination, the lower limit of the hydrogenation rate of the hydrogenated conjugated diene block copolymer is preferably 50% or more, more preferably 60% or more, and further preferably 70% or more. It is generally known that the amount of unsaturated bonds in a hydrogenated conjugated diene block copolymer having a hydrogenation rate of 50% or more is greater than the amount of unsaturated bonds in the acrylic resin generated by a side reaction. By setting the hydrogenation rate of the hydrogenated conjugated diene block copolymer to 50% or more and 90% or less, there is a tendency to be able to satisfy the heat cycle resistance, hot water resistance, heat aging resistance, weather resistance, appearance, and mold contamination resistance of the laminate of the present embodiment.

[0226] That is, from the aspects of heat cycle resistance, hot water resistance, weather resistance, appearance, and mold contamination resistance, it is preferred that the hydrogenated conjugated diene-based copolymer has an amino group, and it is further preferred that the hydrogenation rate of the hydrogenated conjugated diene-based block copolymer having an amino group is 50% to 90%, more preferably 60% to 90%, further preferably 70% to 90%, further more preferably 70% to 88%, further preferably 70% to 86%, and particularly preferably 70% to 85%.

[0227] In addition, decorative laminates used as materials for automobile interior and exterior are required to be lightweight from the perspective of fuel efficiency, and there is a tendency for the layer (I) mainly composed of acrylic resin as a decorative layer to be required to be thinner.

[0228] From the above viewpoint, the thickness of the layer (I) is preferably 1.5 mm or less, more preferably 1.0 mm or less, further preferably 0.7 mm or less, further more preferably 0.5 mm or less, and further preferably 0.3 mm or less.

[0229] When the thickness of the above-mentioned layer (I) is thin, specifically, when it is less than 1.5 mm, from the aspect of the productivity of the laminate of the present embodiment, it is preferred to manufacture a laminate of at least two layers in which layer (I) and layer (III) are in contact, and then laminate to layer (II) to obtain the laminate of the present embodiment. From the aspect of the handleability of the laminate of at least two layers including layer (I) and layer (III), the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer used in layer (III) is preferably 25% by mass or more, more preferably 27% by mass or more, further preferably 30% by mass or more, and further more preferably 33% by mass or more.

[0230] By making the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer 25% by mass or more, the stickiness of layer (III) can be suppressed, and the winding property and / or delivery property of the laminate of at least two layers including layer (I) and layer (III) are good, and there is a tendency that excellent handling properties can be obtained.

[0231] The upper limit of the content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is preferably 80% by mass or less, more preferably 75% by mass or less, further preferably 70% by mass or less, further more preferably 65% ​​by mass or less, further preferably 60% by mass or less, and particularly preferably 55% by mass or less, from the perspective of compatibility with layer (II).

[0232] [Detailed Structure of Hydrogenated Conjugated Diene Block Copolymer]

[0233] The conjugated diene compound constituting the hydrogenated conjugated diene block copolymer used in the adhesive component is a diene having a pair of conjugated double bonds.

[0234] The hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of the following polymer blocks (A) to (C).

[0235] (A) A polymer block mainly composed of vinyl aromatic monomer units (polymer block (A))

[0236] (B) A polymer block mainly composed of a conjugated diene monomer unit (polymer block (B))

[0237] (C) Polymer block having vinyl aromatic monomer units and conjugated diene monomer units (polymer block (C))

[0238] In the polymer block (A) mainly composed of vinyl aromatic monomer units, the content of the vinyl aromatic monomer units is 80% by mass or more.

[0239] Examples of the vinyl aromatic compound for forming the vinyl aromatic monomer unit include, but are not limited to, styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, and N,N-diethyl-p-aminoethylstyrene.

[0240] Among these, styrene, α-methylstyrene, and 4-methylstyrene are preferred from the viewpoint of availability and productivity, and styrene is more preferred.

[0241] The polymer block (A) may be composed of one type of vinyl aromatic monomer units, or may be composed of two or more types of vinyl aromatic monomer units.

[0242] From the viewpoint of the strength of the laminate, the content of the vinyl aromatic monomer unit contained in the polymer block (A) is more than 95% by mass, and preferably 100% by mass (without intentionally adding other compounds).

[0243] In the polymer block (B) mainly composed of a conjugated diene monomer unit, the content of the conjugated diene monomer unit is 80% by mass or more.

[0244] The conjugated diene compound used to form the conjugated diene monomer unit is a diene having a pair of conjugated double bonds. Examples of the diene include, but are not limited to, 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, and farnesene.

[0245] Among these, 1,3-butadiene and isoprene are preferred from the viewpoint of availability and productivity.

[0246] The polymer block (B) may be composed of one type of conjugated diene monomer units, or may be composed of two or more types of conjugated diene monomer units.

[0247] From the viewpoint of impact resistance of the laminate, the content of the conjugated diene monomer unit contained in the polymer block (B) is more than 95% by mass, and preferably 100% by mass (without intentionally adding other compounds).

[0248] The hydrogenated conjugated diene block copolymer may also contain a polymer block (D) composed of a compound copolymerizable with the vinyl aromatic monomer unit and / or the conjugated diene monomer unit other than the vinyl aromatic monomer unit and / or the conjugated diene monomer unit, within a range that does not impair the appearance and / or adhesive strength of the laminate.

[0249] The vinyl aromatic compound and conjugated diene compound used for forming the vinyl aromatic monomer units and conjugated diene monomer units contained in the polymer block (C) having conjugated diene monomer units and vinyl aromatic monomer units may be any compounds that can be used for the polymer block (A) and the polymer block (B).

[0250] There is no particular limitation on the distribution state of the vinyl aromatic monomer units in the polymer block (C). In the polymer block (C), the vinyl aromatic monomer units may be uniformly distributed or tapered. In addition, there may be a plurality of uniformly distributed portions and / or tapered distributed portions of the vinyl aromatic monomer units, respectively, or there may be a plurality of segments having different contents of the vinyl aromatic monomer units.

[0251] From the viewpoint of the compatibility, in the polymer block (C), the mass ratio of the vinyl aromatic monomer unit / the conjugated diene monomer unit is 5 / 95 to 95 / 5, preferably 10 / 90 to 90 / 10, and more preferably 15 / 85 to 85 / 15.

[0252] Thereby, the polymer block (C) can be clearly distinguished from the polymer block (A) and the polymer block (B).

[0253] The hydrogenated conjugated diene block copolymer used in the adhesive component may contain other compounds copolymerizable with the conjugated diene compound and the vinyl aromatic compound.

[0254] The structure of the hydrogenated conjugated diene block copolymer is not particularly limited, and examples thereof include those having a structure represented by the following formula.

[0255] In addition, in the following formula, description of the polar group is omitted.

[0256] (bc) n 、c-(bc) n 、b-(cb) n 、(bc) m -X, (cb) m -X, [(bc) n ] m -X, [(cb) n ] m -X, [c-(bc)n ] m -X、[b-(c-b) n ] m -X、[(b-c) n -b] m -X、[(c-b) n -c] m -X、

[0257] (a-b) n 、b-(a-b) n 、a-(b-a) n 、(a-b) m -X、(b-a) m -X、[(a-b) n ] m -X、[(b-a) n ] m -X、[b-(a-b) n ] m -X、[a-(b-a) n ] m -X、[(a-b) n -a] m -X、[(b-a) n -b] m -X、

[0258] (a-c) n 、c-(a-c) n 、a-(c-a) n 、(a-c) m -X、(c-a) m -X、[(a-c) n ] m -X、[(c-a) n ] m -X、[c-(a-c) n ] m -X、[a-(c-a) n ] m -X、[(a-c) n -a] m -X、[(c-a) n -c] m -X、

[0259] c-(b-a) n 、c-(a-b) n 、

[0260] c-(a-b-a) n 、c-(b-a-b) n 、

[0261] a-c-(b-a) n 、a-c-(a-b) n 、

[0262] a-c-(b-a) n -b、[(a-b-c) n ] m -X、

[0263] [a-(b-c) n ] m -X、[(a-b) n -c] m -X、

[0264] [(a-b-a) n -c] m -X、

[0265] [(b-a-b) n -c] m -X、[(c-b-a) n ] m -X、

[0266] [c-(b-a)n] m -X、[c-(a-b-a) n ] m -X、[c-(b-a-b) n ] m -X

[0267] a-(b-c) n 、a-(c-b) n 、

[0268] a-(c-b-c) n 、a-(b-c-b) n 、

[0269] c-a-(b-c) n 、c-a-(c-b) n 、

[0270] c-a-(b-c) n -b、[(c-b-a) n ] m -X、

[0271] [c-(b-a) n ] m -X、[(c-b) n -a] m -X、

[0272] [(c-b-c) n-a] m -X、

[0273] [(b-c-b) n -a] m -X、[(a-b-c) n ] m -X、

[0274] [a-(b-c) n ] m -X、[a-(c-b-c) n ] m -X、[a-(b-c-b) n ] m -X

[0275] b-(a-c) n 、b-(c-a) n 、

[0276] b-(c-a-c) n 、b-(a-c-a) n 、

[0277] c-b-(a-c) n 、c-b-(c-a) n 、

[0278] c-b-(a-c) n -a、[(c-a-b) n ] m -X、

[0279] [c-(a-b) n ] m -X、[(c-a) n -b] m -X、

[0280] [(c-a-c) n -b] m -X、

[0281] [(b-c-b) n -b] m -X、[(b-a-c) n ] m -X、

[0282] [b-(a-c) n ] m -X、[b-(c-a-c) n ] m -X、[b-(a-c-a) n ] m -X

[0283] In addition, in each of the above general formulae, a represents the above polymer block (A), b represents the above polymer block (B), and c represents the above polymer block (C).

[0284] n is an integer of 1 or more, preferably an integer of 1-5.

[0285] m is an integer of 2 or more, and preferably an integer of 2-11.

[0286] X represents the residue of a coupling agent or the residue of a multifunctional initiator.

[0287] The hydrogenated conjugated diene block copolymer is preferably a polymer whose basic structure is particularly represented by the structural formula of ab, aba, or abab.

[0288] From the perspectives of mechanical strength, impact resistance, abrasion resistance, compatibility, and formability of the laminate of this embodiment, the weight average molecular weight (Mw) of the hydrogenated conjugated diene block copolymer used in the adhesive component (hereinafter also referred to as "Mw") is preferably 35,000 to 600,000, more preferably 40,000 to 400,000, and further preferably 45,000 to 300,000.

[0289] The weight average molecular weight (Mw) of the hydrogenated conjugated diene block copolymer is a weight average molecular weight (Mw) obtained as follows: based on a calibration curve obtained by measurement of commercially available standard polystyrene (prepared using the peak molecular weight of standard polystyrene), the molecular weight of the peak of the chromatogram obtained in the measurement using gel permeation chromatography (GPC) is obtained, thereby obtaining the weight average molecular weight (Mw).

[0290] The molecular weight distribution of the hydrogenated conjugated diene block copolymer before modification can also be determined by measurement using GPC. The molecular weight distribution is the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn).

[0291] The molecular weight distribution of a single peak of the hydrogenated conjugated diene block copolymer measured by GPC is preferably 5.0 or less, more preferably 4.0 or less, further preferably 3.0 or less, and further more preferably 2.5 or less.

[0292] The weight average molecular weight and molecular weight distribution of the hydrogenated conjugated diene block copolymer can be controlled within the above numerical ranges by adjusting polymerization conditions such as the amount of monomer added, the timing of addition, the polymerization temperature, and the polymerization time.

[0293] [Method for producing hydrogenated conjugated diene block copolymer]

[0294] The hydrogenated conjugated diene block copolymer used in the adhesive component of the laminate of the present embodiment can be produced by, for example, but not limited to, the following method: in an organic solvent, an organic alkali metal compound is used as a polymerization initiator, a conjugated diene compound and a vinyl aromatic compound are polymerized to obtain a block copolymer, and then a hydrogenation reaction is carried out, and a modification reaction is carried out as needed to produce the hydrogenated conjugated diene block copolymer.

[0295] The hydrogenation reaction and the modification reaction are not limited to this order, and may be reversed.

[0296] The polymerization method may be batch polymerization, continuous polymerization, or a combination thereof.

[0297] The polymerization temperature is usually 0 to 180°C, preferably 20 to 160°C, more preferably 30 to 150°C.

[0298] The polymerization time varies depending on the target conjugated diene block copolymer, but is usually within 48 hours, preferably 0.1 to 10 hours, and more preferably 0.5 to 5 hours from the viewpoint of obtaining a conjugated diene polymer having a narrow molecular weight distribution and high strength.

[0299] The atmosphere of the polymerization system is not particularly limited as long as the pressure is within a range sufficient to maintain nitrogen and the solvent in a liquid phase.

[0300] It is preferred that no impurities such as water, oxygen, carbon dioxide, etc., which may deactivate the polymerization initiator and the living polymer, are present in the polymerization system.

[0301] Examples of the organic solvent include, but are not limited to, aliphatic hydrocarbons such as n-butane, isobutane, n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, and methylcyclopentane; and aromatic hydrocarbons such as benzene, xylene, toluene, and ethylbenzene.

[0302] As for the organic alkali metal compound as the polymerization initiator, an organic lithium compound is preferred.

[0303] Examples of the organic lithium compound include organic monolithium compounds, organic dilithium compounds, and organic polylithium compounds.

[0304] Examples of the organic lithium compound include, but are not limited to, ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, n-pentyl lithium, n-hexyl lithium, benzyl lithium, phenyl lithium, hexamethylene dilithium, butadienyl lithium, isopropenyl dilithium and piperidine lithium.

[0305] When an organic lithium compound containing N such as piperidine lithium is used as a polymerization initiator, an amino-modified conjugated diene-based block copolymer having an atomic group in which X=0 in NHx is obtained.

[0306] These polymerization initiators may be used alone or in combination of two or more. Among these, n-butyllithium, sec-butyllithium, and piperidine lithium are preferred from the viewpoint of polymerization activity.

[0307] The amount of the organic alkali metal compound used as a polymerization initiator depends on the molecular weight of the desired conjugated diene block copolymer, and is usually preferably in the range of 0.01 to 1.5 phm (parts by mass per 100 parts by mass of the monomer), more preferably 0.02 to 0.3 phm, and even more preferably 0.05 to 0.2 phm.

[0308] The vinyl bond content of the conjugated diene block copolymer can be controlled by using a Lewis base, for example, a compound such as ether or amine as a vinyl bond content adjuster (hereinafter referred to as a vinylating agent).

[0309] In addition, the amount of the vinylating agent used can be adjusted according to the target vinyl bond amount.

[0310] Examples of the vinylating agent include, but are not limited to, ether compounds and tertiary amine compounds.

[0311] Examples of the ether compound include linear ether compounds and cyclic ether compounds.

[0312] Examples of the linear ether compound include, but are not limited to, dimethyl ether, diethyl ether, diphenyl ether, dialkyl ether compounds of ethylene glycol such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and ethylene glycol dibutyl ether, and dialkyl ether compounds of diethylene glycol such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol dibutyl ether.

[0313] Examples of the cyclic ether compound include, but are not limited to, tetrahydrofuran, dioxane, 2,5-dimethyltetrahydrofuran, 2,2,5,5-tetramethyltetrahydrofuran, 2,2-bis(2-tetrahydrofuryl)propane, and alkyl ethers of husk alcohol.

[0314] Examples of tertiary amine compounds include, but are not limited to, trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-ethylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, 1,2-dipiperidinylethane, trimethylaminoethylpiperazine, N,N,N',N",N"-pentamethylethylenetriamine, N,N'-dioctyl-p-phenylenediamine, pyridine, tetramethylpropylenediamine, and bis[2-(N,N-dimethylamino)ethyl]ether.

[0315] These compounds may be used alone or in combination of two or more.

[0316] As the tertiary amine compound, a compound having two amines is preferred. Among these, a compound having a structure showing symmetry in the molecule is more preferred, and N,N,N',N'-tetramethylethylenediamine, bis[2-(N,N-dimethylamino)ethyl]ether, and 1,2-dipiperidinylethane are further preferred.

[0317] In the production process of the conjugated diene block copolymer, a conjugated diene compound and a vinyl aromatic compound may be polymerized in the presence of the vinylating agent, the organic lithium compound, and the alkali metal alkoxide.

[0318] Here, the alkali metal alkoxide is a compound represented by the general formula MOR (wherein M is an alkali metal and R is an alkyl group).

[0319] By allowing an alkali metal alkoxide to coexist in the polymerization step, it is possible to obtain an effect of controlling the vinyl bond amount, molecular weight distribution, polymerization rate, block ratio, and the like.

[0320] As the alkali metal of the alkali metal alkoxide, sodium or potassium is preferred from the viewpoints of high vinyl bond content, narrow molecular weight distribution, high polymerization rate, and high blocking ratio.

[0321] Examples of alkali metal alkoxides include, but are not limited to, sodium alkoxides, lithium alkoxides, and potassium alkoxides having an alkyl group having 2 to 12 carbon atoms, preferably sodium alkoxides and potassium alkoxides having an alkyl group having 3 to 6 carbon atoms, and more preferably sodium tert-butoxide, sodium tert-amylate, potassium tert-butoxide, and potassium tert-amylate.

[0322] Among these, sodium tert-butoxide and sodium tert-amylate, which are sodium alkoxides, are more preferred.

[0323] The method for hydrogenating the unsaturated bonds derived from the conjugated diene monomer units of the conjugated diene block copolymer is not particularly limited. For example, the conjugated diene block copolymer obtained in the above-mentioned polymerization step is hydrogenated by supplying hydrogen in the presence of a hydrogenation catalyst, thereby obtaining a hydrogenated conjugated diene block copolymer in which the double bond residues of the conjugated diene monomer units are hydrogenated.

[0324] The hydrogenation rate (hydrogenation rate) can be controlled, for example, by adjusting the amount of catalyst during hydrogenation, and the hydrogenation rate can be controlled, for example, by adjusting the amount of catalyst during hydrogenation, the amount of hydrogen introduced, the pressure, the temperature, and the like.

[0325] The hydrogenation reaction step is preferably performed after the production reaction of the block copolymer before hydrogenation is stopped.

[0326] When the hydrogenated conjugated diene block copolymer has a polar group, that is, when the above condition (i) is satisfied, at least one polar group selected from the group consisting of anhydride groups, amino groups, dicarboxyl groups, carboxyl groups, epoxy groups and oxetane groups is preferably bonded.

[0327] The method for introducing the above-mentioned polar groups into the conjugated diene block copolymer is not particularly limited, and examples thereof include: a method of introducing the polar groups using a polymerization initiator having the specified functional groups that become the above-mentioned polar groups; a method of polymerizing unsaturated monomers having the functional groups; a method of subjecting a modifier that forms or contains functional groups at the active ends to an addition reaction; and the like.

[0328] Examples of the above-mentioned "modifier" include, but are not limited to, aliphatic carboxylic acids such as maleic acid, oxalic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, tricarboxylic acid, cyclohexanedicarboxylic acid, and cyclopentanedicarboxylic acid, and aromatic carboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, trimesic acid, trimellitic acid, and pyromellitic acid. Examples of the above-mentioned "modifier" include, but are not limited to, maleic anhydride, itaconic anhydride, pyromellitic dianhydride, cis-4-cyclohexane-1,2-dicarboxylic anhydride, 1,2,4,5-pyromellitic dianhydride, 5-(2,5-dioxytetrahydroxyfuranyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, and ε-caprolactam.

[0329] Other methods for introducing polar groups into conjugated diene block copolymers include, for example, reacting an organic alkali metal compound such as an organic lithium compound with a conjugated diene block copolymer (metallization reaction), and adding a modifier having a functional group to a polymer to which an organic alkali metal is added.

[0330] In addition, as another method for introducing a polar group, for example, there can be mentioned a production method of directly graft-adding an atomic group having a functional group to an unmodified conjugated diene block copolymer.

[0331] As the method of graft addition, there can be cited: a method of reacting a free radical initiator, a conjugated diene block copolymer, and the above-mentioned modifier in a solution containing them; or a method of reacting a free radical initiator, a conjugated diene block copolymer, and the above-mentioned modifier under heating and melting; or a method of reacting a conjugated diene block copolymer and a compound containing the above-mentioned modifier under heating and melting without containing a free radical initiator; and the like.

[0332] As the reaction method, the method of melt-kneading each component using common mixers such as Banbury mixer, single screw extruder, twin screw extruder, worm kneader, multi-screw extruder can be enumerated. From the aspect of cost and production stability, the method using single screw extruder, twin screw extruder or multi-screw extruder can be preferably enumerated, and the method using twin screw extruder can be more preferably enumerated.

[0333] In the reaction step, the raw materials may be added all at once after dry mixing, or each raw material may be added separately, and the same raw material may be added in stages.

[0334] From the viewpoint of uniform addition of the modifier, the screw speed is preferably 50 to 400 rpm, more preferably 100 to 350 rpm, and from the viewpoint of uniform addition of the modifier while preventing resin degradation due to shearing, the screw speed is preferably 150 to 300 rpm.

[0335] The kneading temperature is preferably 100° C. to 350° C. from the viewpoint of becoming a temperature at which the conjugated diene block copolymer melts and a temperature at which free radicals are generated by the free radical initiator. It is more preferably 120° C. to 300° C., and even more preferably 150° C. to 250° C. from the viewpoint of controlling the amount of addition and suppressing the degradation of the resin due to heat.

[0336] In order to suppress deactivation of radical active species by oxygen, melt kneading is preferably performed under an inert gas condition such as nitrogen.

[0337] Examples of free radical initiators include, but are not limited to, ketone peroxides, peroxyketals, hydrogen peroxides, dialkyl peroxides, diacyl peroxides, peroxyesters, and peroxydicarbonates. Preferably, the free radical initiator has a one-minute half-life temperature in the kneading temperature range, and more preferably, the one-minute half-life temperature is between 150°C and 250°C. Examples of such free radical initiators include, but are not limited to, 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, 2,2-di(4,4-di-(tert-butylperoxy)cyclohexyl)propane, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxymaleate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoyl peroxide)hexane, Tert-butyl peroxyacetate, 2,2-di-(tert-butylperoxy)butane, tert-butyl peroxybenzoate, n-butyl-4,4-di-(tert-butylperoxy)valerate, di(2-tert-butylperoxyisopropyl)benzene, dicumyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylcumyl peroxide, di-tert-butyl peroxide, p-methane hydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide.

[0338] In particular, from the perspective of compatibility with the conjugated diene block copolymer, di(2-tert-butylperoxyisopropyl)benzene, dicumyl peroxide, di-tert-hexyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butylcumyl peroxide, di-tert-butyl peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne are preferred. In particular, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne are more preferred.

[0339] Another method for introducing a polar group into a conjugated diene block copolymer is secondary modification in which a primary modified conjugated diene block copolymer obtained by the above method is reacted with an atomic group having a functional group to introduce the polar group.

[0340] As the combination of polar groups, for example, there can be mentioned an amino group and a dicarboxyl group, an acid anhydride group and an amino group, a hydroxyl group; an isocyanate group and a hydroxyl group, a carboxyl group and an amino group, an acid anhydride group and a hydroxyl group, a silanol group and a hydroxyl group, an epoxy group and a carboxyl group. From the aspect of reactivity, a combination of an amino group and a dicarboxyl group, an acid anhydride group and an amino group, a silanol group and a hydroxyl group, a dicarboxyl group and an amino group, an epoxy group and a carboxyl group is preferred, and a combination of an amino group and a dicarboxyl group, an acid anhydride group and an amino group is more preferred.

[0341] As a method for bonding an epoxy group, an acid anhydride group or a hydroxyl group to the conjugated diene block copolymer as a primary modification, the above-mentioned method can be mentioned, and as a modifier, the above-mentioned modifiers and a polymerizable compound containing an epoxy group can be mentioned.

[0342] As a method for bonding a silanol group to a conjugated diene block copolymer as a primary modification, the above-mentioned method can be cited, and as a modifier, bis-(3-triethoxysilylpropyl)-tetrasulfane, bis-(3-triethoxysilylpropyl)-disulfane, ethoxysiloxane oligomers, polymerizable compounds containing epoxy groups, hydrolyzates of compounds having alkoxysilyl groups listed in the above-mentioned polymerizable compounds containing epoxy groups, etc. can be cited.

[0343] As a method for bonding an amino group to a conjugated diene block copolymer as a primary modification, the above-mentioned method can be mentioned, and as a modifier, for example, 1,3-dimethyl-2-imidazolidinone, 1,3-diethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, 1,3-diethyl-2-imidazolidinone, 1,3-dipropyl-2-imidazolidinone, 1-methyl-3-ethyl-2-imidazolidinone, 1-methyl-3-propyl-2-imidazolidinone, 1-methyl-3-butyl-2-imidazolidinone, 1-methyl-3-(2-methoxyethyl)-2-imidazolidinone, 1-methyl-3-(2-ethoxyethyl)-2-imidazolidinone, 1,3-di-(2-ethoxyethyl)-2-imidazolidinone, 1,3-dimethylethylenethiourea, N,N'-diethylpropyleneurea, N-methyl-N'-ethylpropyleneurea, etc. can be mentioned.

[0344] In addition, examples of the modifier include 1-methyl-2-pyrrolidone, 1-cyclohexyl-2-pyrrolidone, 1-ethyl-2-pyrrolidone, 1-propyl-2-pyrrolidone, 1-butyl-2-pyrrolidone, 1-isopropyl-2-pyrrolidone, 1,5-dimethyl-2-pyrrolidone, 1-methoxymethyl-2-pyrrolidone, 1-methyl-2-piperidone, 1,4-dimethyl-2-piperidone, 1-ethyl-2-piperidone, 1-isopropyl-2-piperidone, and 1-isopropyl-5,5-dimethyl-2-piperidone.

[0345] As a method for bonding a primary modified conjugated diene polymer having an amino group bonded thereto and a secondary modifier, the above-mentioned method can be cited, and as the modifier, aliphatic carboxylic acids such as maleic acid, oxalic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, tricarboxylic acid, cyclohexanedicarboxylic acid, and cyclopentanedicarboxylic acid, and aromatic carboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, trimesic acid, trimellitic acid, and pyromellitic acid can be cited.

[0346] Other examples include maleic anhydride, itaconic anhydride, pyromellitic dianhydride, cis-4-cyclohexane-1,2-dicarboxylic anhydride, 1,2,4,5-pyromellitic dianhydride, and 5-(2,5-dioxytetrahydroxyfuranyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride.

[0347] The shape of the obtained polar group-containing conjugated diene block copolymer is not particularly limited, and examples thereof include pellets, sheets, strands, chips, etc. Alternatively, a molded article may be directly produced after melt kneading.

[0348] [Method for producing laminate]

[0349] The laminate of the present embodiment is a laminate of two or three or more layers including the above-mentioned layers and components, and can be produced by widely adopting a known method.

[0350] The method for producing the laminate is not limited, and various conventionally known methods can be adopted.

[0351] The laminate of the present embodiment has good adhesiveness, and can be produced by the following molding method without performing dry lamination using an organic solvent or the like.

[0352] As molding methods, for example, there can be cited: a method of producing a blown film, a T-die film, a sheet, a tube, etc. by a co-extrusion method in which molten resins melted by an extruder are supplied to a multi-layer mold and stacked in the mold to form; and co-injection molding in which molten resins are injected into the same mold with a time lag.

[0353] Alternatively, extrusion lamination molding may be employed in which a resin film constituting any one of the layers is preliminarily molded and the other layer is melt-extruded thereon.

[0354] Alternatively, a laminate may be formed by pre-molding resin films constituting the respective layers, and applying heat to the respective layers to fuse them.

[0355] A stretched laminate may be formed by obtaining a laminate by the above-mentioned molding method and then stretching the laminate.

[0356] The stretched laminate may be heat-set or may be made into a product without heat-setting. If heat-setting is not performed, the stretched laminate can be used as a shrink film because it has the property of shrinking by releasing stress when the stretched laminate is subsequently heated. In addition, it can be made into a deep-drawn container or the like by undergoing secondary processing such as vacuum forming or pressure forming.

[0357] In addition, when the laminate has an adhesive layer (III), an adhesive layer (layer (III)) can be provided in advance on both sides of the adherend (layer (I), layer (II)), and then the adherends are laminated for bonding. In order to firmly bond, the laminate can be pressurized, and the pressurization can be applied to the entire body or only to the portion provided with the adhesive layer. There is no particular restriction on the pressurization method, and there is no particular restriction on the pressure as long as the pressure is such that the adhesive layer does not deform significantly.

[0358] The shape of the laminate is not limited, and may be any shape, such as a flat shape such as a film, a sheet, or a plate, a tube shape, a bag shape, or an amorphous shape.

[0359] The laminate of the present embodiment may also include layers other than the layer (I) mainly composed of an acrylic resin, the layer (II) mainly composed of a polyolefin resin, the adhesive layer (III), and the layer (IV) containing a polyolefin resin and an adhesive component (hereinafter sometimes referred to as other layers).

[0360] The material constituting the other layers is not limited, and they may be not only resin layers but also metal layers.

[0361] The materials of other resin layers constituting the laminate are not limited, and examples thereof include the following thermoplastic resins or various thermoplastic elastomers: polyolefin resins (excluding substances contained in layer (II)); polyphenylene ether resins; polyamide resins such as nylon 6, nylon 66, and nylon 11; polyester resins such as polyethylene terephthalate and polybutylene terephthalate (excluding substances contained in component (A)); (meth)acrylic resins such as polymethyl methacrylate resins; styrene resins such as polystyrene; and the like.

[0362] Furthermore, various additives and the like may be blended into each layer of the laminate within a range not hindering the effects of the present invention.

[0363] Examples of additives include various heat stabilizers, antioxidants, ultraviolet absorbers, light stabilizers, anti-aging agents, nucleating agents, plasticizers, impact modifiers, compatibilizers, defoamers, thickeners, crosslinking agents, surfactants, lubricants, mold release agents, anti-blocking agents, processing aids, antistatic agents, flame retardants, flame retardant aids, fillers, colorants, etc. These additives may be used alone or in any combination and ratio.

[0364] Examples of the heat stabilizer and antioxidant include hindered phenols, phosphorus compounds, hindered amines, sulfur compounds, copper compounds, and alkali metal halides.

[0365] Flame retardants can be roughly divided into halogen flame retardants and non-halogen flame retardants. From the environmental point of view, non-halogen flame retardants are preferred. Examples of non-halogen flame retardants include phosphorus flame retardants, hydrated metal compound (aluminum hydroxide, magnesium hydroxide) flame retardants, nitrogen-containing compound (melamine, guanidine) flame retardants, and inorganic compound (borates, molybdenum compounds) flame retardants.

[0366] Filling materials can be roughly divided into organic filling materials and inorganic filling materials. As organic filling materials, polymers of natural origin such as starch, cellulose particles, wood powder, bean dregs, rice husks, bran, or their modified products can be cited. In addition, as inorganic filling materials, talc, calcium carbonate, zinc carbonate, wollastonite, silicon oxide, aluminum oxide, magnesium oxide, calcium silicate, sodium aluminate, calcium aluminate, sodium aluminosilicate, magnesium silicate, glass hollow spheres, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, metal fiber, metal whisker, ceramic whisker, potassium titanate, boron nitride, graphite, carbon fiber, etc. can be cited.

[0367] When the laminate of the present embodiment has a layer (IV) containing an adhesive component and a polyolefin resin, a resin composition containing a polyolefin resin and an adhesive component can be obtained by mixing the above components at a predetermined ratio.

[0368] About the method of mixing, as long as the raw material components are uniformly dispersed, there is no particular restriction. That is, the resin combination uniformly dispersed by each component can be obtained by mixing the above-mentioned raw material components etc. simultaneously or in any order. In order to mix and disperse more evenly, the above-mentioned raw material components of a specified amount are preferably melt-mixed, for example, each raw material component of a resin combination etc. can be heated after being mixed in any order, or all raw material components etc. can be melted successively while mixing, and each raw material can be suitably mixed (dry blending) to carry out melt mixing during the molding when manufacturing the target molded body.

[0369] About mixing method, mixing conditions, as long as each raw material component etc. is uniformly mixed, there is no particular restriction, from the aspect of productivity, the following method is preferred: use for example drum mixer, V-type blender, ribbon mixer, Henschel mixer etc. to mix raw materials, utilize single screw extruder, twin screw extruder and other continuous mixer and roll, Banbury mixer, pressure kneading machine and other batch mixers to carry out melt mixing. The manufacturing conditions when utilizing these methods to manufacture resin composition are not limited, and can be suitably set under known conditions. About the temperature during melt mixing, as long as it is the temperature at which at least one of each raw material component becomes a molten state, the temperature at which all the components used are melted is usually selected, and generally can be carried out at 150 to 250 ° C.

[0370] (Preferred embodiment of the method for producing a laminate)

[0371] The method for producing the laminate according to the present embodiment is particularly preferably the following method.

[0372] That is, in a method for manufacturing a laminate having a layer (I) mainly composed of an acrylic resin, a layer (II) mainly composed of a polyolefin resin, and an adhesive layer (III) arranged between the above-mentioned layer (I) and the above-mentioned layer (II), it is preferred that the manufacturing method includes the following steps: a step of laminating the above-mentioned layer (I) in such a manner that the above-mentioned layer (III) is in contact with the above-mentioned layer (III) to obtain a laminate of at least two layers; and a step of laminating layer (II) in such a manner that the above-mentioned layer (III) of the above-mentioned laminate of at least two layers is in contact with the above-mentioned layer (II).

[0373] This production method is suitable when the layer (I) is a thin layer with a thickness of 1.5 mm or less.

[0374] In addition, from the perspective of obtaining a laminate having excellent appearance, heat cycle resistance and / or hot water resistance, in the process of laminating the above-mentioned layer (I) and the above-mentioned layer (III), it is preferred to laminate the layer (I) and the layer (III) in a molten state and cool them to thereby perform the lamination.

[0375] The molding method is not particularly limited, and examples thereof include a molding method of forming an inflation film, a T-die film, or the like by a co-extrusion method in which each molten resin melted by an extruder is supplied to a multilayer die and laminated in the die to form an inflation film or a T-die film.

[0376] In addition, from the perspective of productivity, in the process of obtaining a laminate of at least two layers in which the above-mentioned layer (I) is in contact with the above-mentioned layer (III), and further laminating the above-mentioned layer (II) on the above-mentioned laminate, the following process can be performed: the above-mentioned laminate of at least two layers is installed in a mold, the polyolefin resin constituting the above-mentioned layer (II) is allowed to flow into the above-mentioned mold while being molten, and it is cooled, thereby laminating to obtain the laminate of the present embodiment as the target object.

[0377] Example

[0378] The present embodiment will be described in detail below with reference to specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples.

[0379] The structure and physical property measurement methods of the hydrogenated conjugated diene block copolymer used as the adhesive component in Examples and Comparative Examples, and the evaluation method of the laminate are as follows.

[0380] [Structure and physical properties of hydrogenated conjugated diene block copolymer and evaluation of laminate]

[0381] The structure and physical property measurement methods of the hydrogenated conjugated diene polymer are as follows.

[0382] ((1) Vinyl Bond Amount of Hydrogenated Conjugated Diene Block Copolymer)

[0383] In the hydrogenated conjugated diene block copolymer, the vinyl bond content relative to a total of 100 mol% of the conjugated diene monomer units was determined by proton nuclear magnetic resonance (NMR) of the hydrogenated conjugated diene block copolymer. 1 H-NMR) was used for determination.

[0384] The measurement equipment used was ECS400 (manufactured by JEOL), the solvent used was deuterated chloroform, the sample concentration was set to 50 mg / mL, the observation frequency was set to 400 MHz, tetramethylsilane was used as the chemical shift standard, and the measurement was performed under the conditions of pulse delay of 2.904 seconds, scan number of 64 times, pulse width of 45°, and measurement temperature of 26°C.

[0385] The vinyl bond amount was calculated from the integrated values ​​of the signals attributable to the 1,4-bond and the 1,2-bond, and the integrated value per 1H of each bonding form was calculated. Thereafter, the vinyl bond amount was calculated from the ratio of the 1,4-bond to the 1,2-bond.

[0386] ((2) Hydrogenation rate of unsaturated bonds of conjugated diene monomer units in hydrogenated conjugated diene block copolymer)

[0387] The hydrogenation rate of the hydrogenated conjugated diene copolymer was determined by proton nuclear magnetic resonance ( 1 H-NMR) was used for determination.

[0388] The measurement conditions and the method of processing the measurement data are the same as those in (1) above.

[0389] The hydrogenation rate was calculated by calculating the integrated value of the signal derived from the remaining double bond at 4.5 to 5.5 ppm and the signal derived from the hydrogenated conjugated diene, and then calculating the ratio thereof.

[0390] ((3) Content of vinyl aromatic monomer units in hydrogenated conjugated diene block copolymer (hereinafter also referred to as "styrene content"))

[0391] The content of vinyl aromatic monomer units was determined by proton nuclear magnetic resonance (NMR) of hydrogenated conjugated diene block copolymers. 1 H-NMR) method.

[0392] The measurement equipment used was ECS400 (manufactured by JEOL), the solvent used was deuterated chloroform, the sample concentration was 50 mg / mL, the observation frequency was 400 MHz, the chemical shift standard was tetramethylsilane, and the measurement was performed under the conditions of pulse delay 2.904 seconds, scan number 64 times, pulse width 45°, and measurement temperature 26°C.

[0393] The styrene content was calculated using the integrated value of the total styrene aromatic signal at 6.2 to 7.5 ppm in the spectrum.

[0394] Alternatively, the styrene content can be confirmed by calculating the content of the vinyl aromatic monomer unit for each polymer sampled at each step of the polymerization process of the conjugated diene block copolymer before hydrogenation.

[0395] ((4) Weight Average Molecular Weight of Hydrogenated Conjugated Diene Block Copolymer)

[0396] The weight average molecular weight of the hydrogenated conjugated diene block copolymer was measured by GPC [apparatus: HLC8220 (manufactured by Tosoh Corporation), column: TSK gel SUPER-HZM-N (4.6 mm×30 cm)].

[0397] Tetrahydrofuran was used as a solvent.

[0398] The weight average molecular weight was determined from the peak molecular weight of the chromatogram using a calibration curve obtained by measurement of commercially available standard polystyrene (created using the peak molecular weight of standard polystyrene).

[0399] In addition, when the molecular weight has a plurality of peaks in the chromatogram, the weight average molecular weight is determined from the molecular weight of each peak and the composition ratio of each peak (determined from the area ratio of each peak in the chromatogram).

[0400] ((5) Modification Ratio of Amino-Modified Hydrogenated Conjugated Diene Block Copolymer)

[0401] Using the property that the modified component will be adsorbed to a GPC column using silica gel as a packing material, for a sample solution containing a hydrogenated conjugated diene block copolymer and a low molecular weight internal standard polystyrene (PS), the ratio of the hydrogenated conjugated diene block copolymer to the standard polystyrene in the chromatogram measured in the above (5) is compared with the ratio of the hydrogenated conjugated diene block copolymer to the standard polystyrene in the chromatogram measured using a silica column GPC [apparatus: LC-10 (manufactured by Shimadzu Corporation), column: Zorbax (manufactured by DuPont)], and the adsorption amount on the silica column is determined from the difference between them, and this ratio is taken as the modification rate.

[0402] The modification rate was calculated by the following formula as the ratio (%) of the amino group having a specific structure at the end.

[0403] [Number 1]

[0404]

[0405] a: Area of ​​all polymers measured using polystyrene gel (PLgel) (%)

[0406] b: Area (%) of low molecular weight internal standard PS measured by polystyrene gel (PLgel)

[0407] c: Area of ​​total polymer measured by Zorbax column (%)

[0408] d: Area (%) of low molecular weight internal standard PS measured using a silica column (Zorbax)

[0409] ((6) Modification Ratio of Maleic Anhydride-Modified Hydrogenated Conjugated Diene Block Copolymer)

[0410] The hydrogenated conjugated diene block copolymer modified with maleic anhydride was dissolved in toluene and titrated with a methanol solution of sodium methoxide with a coefficient of 1±0.05 to perform calculation.

[0411] Evaluation of the characteristics of the laminate was performed as follows.

[0412] ((7) Adhesion (adhesion strength))

[0413] In Examples 1 to 31 and Comparative Examples 1 to 12, the laminate described below was left to stand for 24 hours at a temperature of 25° C. and a humidity of 50%, and then a 1 cm wide incision was made in the layer (II) of the laminate containing polypropylene resin as the main component or the layer (IV) of the laminate containing polypropylene resin and adhesive components described below, and a peel test of 10 cm or more was performed using a tensile testing machine, and the bonding strength (N / m) was calculated from the obtained stress. The higher the bonding strength, the better the bonding property.

[0414] In Examples 32 to 40 and Comparative Examples 13 to 15, the evaluation was performed by the cross-cut test according to JIS K 5400. After the laminate described below was left to stand for 24 hours at a temperature of 25° C. and a humidity of 50%, 100 1 mm2 sections were cut out from the side of the layer (I) mainly composed of acrylic resin until the adhesive layer (III) was reached. 2A cellophane tape (registered trademark, manufactured by Michibond Co., Ltd., CT28) was pressed from above the above cut with fingers, adhered to the layer (I) mainly composed of acrylic resin, and then peeled off. The case where the layer (I) mainly composed of acrylic resin did not peel off in all the four squares in 100 cuts was regarded as a residual rate of 100%, and the evaluation was carried out according to the following criteria.

[0415] : Residual rate more than 95%

[0416] ○: Residual rate 80% or more

[0417] △: Residual rate is greater than 50%

[0418] ×: Residual rate 50% or less

[0419] ((8) Impact resistance)

[0420] After the laminate (100mm×100mm) is kept at 23°C (normal temperature) or -30°C for more than 24 hours, 2 cm of the four sides of the laminate are fixed, and a steel ball with a mass of 1.04kg is freely dropped from a height of 1.0m and 0.5m onto the laminate, and the evaluation is performed according to the following criteria.

[0421] ○: The steel ball does not penetrate, and the broken fragments do not fly around.

[0422] △: The steel ball penetrates, but the broken pieces do not fly around.

[0423] ×: The steel ball penetrated and the broken fragments flew.

[0424] ((9) Vibration Damping)

[0425] The loss factor of the laminate at room temperature was calculated by the cantilever beam method and the half-width method in accordance with JIS K 7391.

[0426] Regarding the excitation method, a non-contact electromagnetic exciter was used for steady-state excitation.

[0427] Evaluation was performed based on the obtained loss factor according to the following criteria.

[0428] ○: 0.020 or more

[0429] ×: less than 0.020

[0430] ((10) Appearance)

[0431] The layer (I) mainly composed of an acrylic resin of the laminate was visually observed, and the appearance was evaluated based on the following criteria.

[0432] : No white turbidity.

[0433] ○: Slightly turbid.

[0434] △: Air bubbles are slightly present (no turbidity or slightly turbidity).

[0435] ×: White turbidity and / or a large number of bubbles are present.

[0436] ((11) Mold contamination)

[0437] In the production of the laminate described below, the mold was visually observed 20 times in succession, and the appearance was evaluated according to the following criteria.

[0438] ○: No mold contamination.

[0439] △: Slight mold contamination.

[0440] ×: There is mold contamination.

[0441] ((12) Heat cycle resistance)

[0442] The laminate described below was subjected to a heat cycle test of 100 cycles, with -40°C / 15 minutes and 80°C / 15 minutes as one cycle, and then returned to room temperature. Thereafter, the adhesiveness (adhesive strength) was evaluated by a cross-cut test in accordance with JIS K 5400 in the same manner as in (7) above. The residual rate obtained in (7) above was compared with the residual rate obtained in the cross-cut test after the heat cycle test, and the reduction rate of the adhesive strength after the heat cycle test was evaluated according to the following criteria.

[0443] : 5% or less

[0444] ○: 15% or less

[0445] △: less than 30%

[0446] ×: 30% or more

[0447] ((13) Hot water resistance)

[0448] The laminate described below was immersed in hot water at 40° C. for 24 hours, then taken out and the water was wiped off.

[0449] Thereafter, the adhesiveness (adhesive strength) was evaluated by the cross-cut test in accordance with JIS K 5400 in the same manner as in (7) above. The residual rate obtained in (7) above was compared with the residual rate obtained in the cross-cut test after the hot water immersion, and the reduction rate of the adhesive strength after the hot water immersion was evaluated according to the following criteria.

[0450] : 5% or less

[0451] ○: 15% or less

[0452] △: less than 30%

[0453] ×: 30% or more

[0454] ((14) Delivery)

[0455] In the two-layer films composed of a layer (I) mainly composed of an acrylic resin and a layer (III) mainly composed of a polyolefin resin in the later-described Examples 32 to 40 and Comparative Examples 13 to 35, co-extrusion molding is performed using the later-described multi-layer T-die extruder, and after winding, the feedability is evaluated according to the following criteria.

[0456] ○: Can be sent

[0457] ×: Cannot send

[0458] [Hydrogenated conjugated diene block copolymer]

[0459] (Modifier)

[0460] As a modifier for producing the hydrogenated conjugated diene block copolymer, the following compounds were used.

[0461] Maleic anhydride (manufactured by Fuso Chemical Industries, Ltd.)

[0462] 1,3-Dimethyl-2-imidazolidinone (all manufactured by Tokyo Chemical Industry Co., Ltd.)

[0463] (Preparation of Hydrogenation Catalyst)

[0464] The hydrogenation catalyst used in the hydrogenation reaction of the hydrogenated conjugated diene copolymer was prepared by the following method.

[0465] 1 L of dried and purified cyclohexane was placed in a nitrogen-purged reaction container, and 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. An n-hexane solution containing 200 mmol of trimethylaluminum was added while stirring thoroughly, and the mixture was reacted at room temperature for about 3 days to obtain a hydrogenation catalyst.

[0466] (Production of Hydrogenated Conjugated Diene Block Copolymer)

[0467] A hydrogenated conjugated diene block copolymer is prepared as follows using a vinyl aromatic compound and a conjugated diene.

[0468] The physical properties are shown in Tables 1 to 3.

[0469] It should be noted that in the "Structure" in Tables 1 to 3, A represents a polymer block (A) mainly composed of a vinyl aromatic monomer unit, B represents a polymer block (B) mainly composed of a conjugated diene monomer unit, and C represents a polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit.

[0470] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (1)>

[0471] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0472] First, a cyclohexane solution (concentration: 20% by mass) containing 15 parts by mass of styrene was added.

[0473] Next, 0.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.25 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0474] Next, a cyclohexane solution containing 70 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 30 minutes.

[0475] Next, a cyclohexane solution (concentration: 20% by mass) containing 15 parts by mass of styrene was added, and polymerization was carried out at 70° C. for 15 minutes.

[0476] Thereafter, methanol was added to terminate the polymerization reaction, thereby obtaining a conjugated diene copolymer.

[0477] Next, the hydrogenation catalyst prepared above was added to the obtained conjugated diene copolymer in an amount of 70 ppm based on Ti per 100 parts by mass of the conjugated diene copolymer, and a hydrogenation reaction was performed at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0478] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (1).

[0479] The hydrogenated conjugated diene block copolymer (1) obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.1×10 4 , the vinyl bonding content is 35% and the hydrogenation rate is 98%.

[0480] The hydrogenated conjugated diene block copolymer (1) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210° C. to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (1)-M.

[0481] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (1)-M was titrated under the above conditions. The modification rate was 1.1% by mass.

[0482] <Hydrogenated conjugated diene block copolymer (2)>

[0483] The same operation as in the hydrogenated conjugated diene block copolymer (1) was carried out except that 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as "DMI") was added to 1 mol of n-butyllithium before adding methanol, and the reaction was carried out at 70°C for 15 minutes. After the reaction, methanol was added.

[0484] The terminal amine-modified hydrogenated conjugated diene block copolymer (2) obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bond content is 35%, the modification rate is 80% (the number of modified groups per polymer chain is 0.80), and the hydrogenation rate is 74%.

[0485] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (3)>

[0486] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0487] First, a cyclohexane solution containing 20 parts by mass of styrene (concentration: 20% by mass) was added.

[0488] Next, 0.041 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.16 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0489] Next, a cyclohexane solution (concentration: 20% by mass) containing 45 parts by mass of styrene and 35 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 45 minutes.

[0490] Next, 0.5 mol of ethyl benzoate was added to 1 mol of n-butyl lithium, and the mixture was reacted at 70° C. for 10 minutes. Methanol was then added to terminate the polymerization reaction.

[0491] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0492] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (3).

[0493] The hydrogenated conjugated diene block copolymer (3) obtained as described above had a styrene content of 65% by mass and a weight average molecular weight of 19.0×10 4 , the vinyl bonding content is 25% and the hydrogenation rate is 98%.

[0494] The hydrogenated conjugated diene block copolymer (3) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210° C. to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (3)-M.

[0495] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (3)-M was titrated under the above conditions. The modification rate was 0.5% by mass.

[0496] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (4)>

[0497] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0498] First, a cyclohexane solution (concentration: 20% by mass) containing 6.0 parts by mass of styrene was added.

[0499] Next, 0.073 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.5 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0500] Next, a cyclohexane solution (concentration: 20% by mass) containing 8.0 parts by mass of styrene and 80 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 45 minutes.

[0501] Then, a cyclohexane solution (concentration: 20% by mass) containing 6.0 parts by mass of styrene was added, and polymerization was carried out at 70° C. for 15 minutes. Methanol was then added to terminate the polymerization reaction.

[0502] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0503] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (4).

[0504] The hydrogenated conjugated diene block copolymer (4) obtained as described above had a styrene content of 20% by mass and a weight average molecular weight of 14.0×10 4 , the vinyl bonding content is 45% and the hydrogenation rate is 98%.

[0505] The hydrogenated conjugated diene block copolymer (4) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210° C. to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (4)-M.

[0506] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (4)-M was titrated under the above conditions. The modification rate was 0.8% by mass.

[0507] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (5)>

[0508] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0509] First, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added.

[0510] Next, 0.062 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 1.5 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 60° C. for 15 minutes.

[0511] Next, a cyclohexane solution (concentration: 20% by mass) containing 5 parts by mass of styrene and 80 parts by mass of butadiene was added, and polymerization was carried out at 60° C. for 45 minutes.

[0512] Then, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 15 minutes. Methanol was then added to terminate the polymerization reaction.

[0513] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0514] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (5).

[0515] The hydrogenated conjugated diene block copolymer (5) obtained as described above had a styrene content of 20% by mass and a weight average molecular weight of 15.0×10 4 , the vinyl bonding content is 71% and the hydrogenation rate is 98%.

[0516] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (6)>

[0517] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0518] First, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added.

[0519] Next, 0.062 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 1.5 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 60° C. for 15 minutes.

[0520] Next, a cyclohexane solution (concentration: 20% by mass) containing 20 parts by mass of styrene and 65 parts by mass of butadiene was added, and polymerization was carried out at 60° C. for 45 minutes.

[0521] Then, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 15 minutes. Methanol was then added to terminate the polymerization reaction.

[0522] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0523] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (6).

[0524] The hydrogenated conjugated diene block copolymer (6) obtained as described above had a styrene content of 35% by mass and a weight average molecular weight of 15.0×10 4 , the vinyl bonding content is 70% and the hydrogenation rate is 98%.

[0525] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (7)>

[0526] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0527] First, a cyclohexane solution containing 22.5 parts by mass of styrene (concentration: 20% by mass) was added.

[0528] Next, 0.079 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 1.5 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 60° C. for 20 minutes.

[0529] Next, a cyclohexane solution containing 55 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 35 minutes.

[0530] Next, a cyclohexane solution containing 22.5 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 20 minutes. Methanol was then added to terminate the polymerization reaction.

[0531] Next, the hydrogenation catalyst prepared above was added to the conjugated diene copolymer obtained above in an amount of 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0532] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (7).

[0533] The hydrogenated conjugated diene block copolymer (7) obtained as described above had a styrene content of 45% by mass and a weight average molecular weight of 11.0×10 4 , the vinyl bonding content is 71% and the hydrogenation rate is 98%.

[0534] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (8)>

[0535] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0536] First, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added.

[0537] Next, 0.066 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 1.5 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 60° C. for 15 minutes.

[0538] Next, a cyclohexane solution containing 85 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 60 minutes.

[0539] Then, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 15 minutes. Methanol was then added to terminate the polymerization reaction.

[0540] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0541] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (8).

[0542] The hydrogenated conjugated diene block copolymer (8) obtained as described above had a styrene content of 15% by mass and a weight average molecular weight of 16.0×10 4 , the vinyl bonding content is 70% and the hydrogenation rate is 98%.

[0543] The hydrogenated conjugated diene block copolymer (8) obtained as described above is mixed with maleic anhydride and supplied to a twin-screw extruder in which the temperature of the entire extruder length is set at 150 to 210°C to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (8)-M.

[0544] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (8)-M was titrated under the above conditions. The modification rate was 0.8% by mass.

[0545] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (9)>

[0546] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0547] First, a cyclohexane solution (concentration: 20% by mass) containing 15 parts by mass of styrene was added.

[0548] Next, 0.066 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 1.5 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 60° C. for 20 minutes.

[0549] Next, a cyclohexane solution containing 70 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 50 minutes.

[0550] Then, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 20 minutes. Methanol was then added to terminate the polymerization reaction.

[0551] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0552] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated conjugated diene block copolymer.

[0553] The hydrogenated conjugated diene block copolymer obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 16.1×10 4 , the vinyl bonding content is 70% and the hydrogenation rate is 98%.

[0554] The hydrogenated conjugated diene block copolymer obtained as described above is mixed with maleic anhydride and supplied to a twin-screw extruder set at a temperature of 150 to 210°C over the entire length of the extruder to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (9)-M.

[0555] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (9)-M was titrated under the above conditions, and the modification rate was 0.7% by mass.

[0556] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (10)>

[0557] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0558] First, a cyclohexane solution containing 7.5 parts by mass of styrene (concentration: 20% by mass) was added.

[0559] Next, 0.15 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.27 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0560] Next, a cyclohexane solution containing 85 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 60° C. for 50 minutes.

[0561] Then, a cyclohexane solution (concentration: 20% by mass) containing 7.5 parts by mass of styrene was added, and polymerization was carried out at 70° C. for 15 minutes. Methanol was then added to terminate the polymerization reaction.

[0562] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0563] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (10).

[0564] The hydrogenated conjugated diene block copolymer (10) obtained as described above had a styrene content of 15% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bonding content is 35% and the hydrogenation rate is 98%.

[0565] The hydrogenated conjugated diene block copolymer (10) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210° C. to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (10)-M.

[0566] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (10)-M was titrated under the above conditions. The modification rate was 1.2% by mass.

[0567] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (11)>

[0568] The same operation as in the hydrogenated conjugated diene block copolymer (10) was carried out except that 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as "DMI") was added to 1 mol of n-butyl lithium before adding methanol, and the reaction was carried out at 70° C. for 15 minutes. After the reaction, methanol was added.

[0569] The terminal amine-modified conjugated diene block copolymer (11) obtained as described above had a styrene content of 15% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bond content is 35%, the modification rate is 80% by mass (the number of modified groups per polymer chain is 0.80), and the hydrogenation rate is 75%.

[0570] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (12)>

[0571] The same operation as the hydrogenated conjugated diene block copolymer (3) was performed except that 0.90 mol of tetramethylethylenediamine (TMEDA) was added relative to 1 mol of n-butyllithium. The obtained hydrogenated conjugated diene block copolymer (12) had a styrene content of 65% by mass and a weight average molecular weight of 19.1×10 4 , the vinyl bonding content is 54% and the hydrogenation rate is 98%.

[0572] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (13)>

[0573] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0574] First, a cyclohexane solution containing 50 parts by mass of styrene (concentration: 20% by mass) was added.

[0575] Next, 0.041 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.90 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 30 minutes.

[0576] Next, a cyclohexane solution (concentration: 20% by mass) containing 15 parts by mass of styrene and 35 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 35 minutes.

[0577] Next, 0.5 mol of ethyl benzoate was added to 1 mol of n-butyl lithium, and the mixture was reacted at 70° C. for 10 minutes. Methanol was then added to terminate the polymerization reaction.

[0578] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0579] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (13).

[0580] The hydrogenated conjugated diene block copolymer (13) obtained as described above had a styrene content of 65% by mass and a weight average molecular weight of 19.0×10 4 , the vinyl bonding content is 55% and the hydrogenation rate is 98%.

[0581] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (14)>

[0582] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0583] First, a cyclohexane solution containing 37.5 parts by mass of styrene (concentration: 20% by mass) was added.

[0584] Next, 0.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.25 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 35 minutes.

[0585] Next, a cyclohexane solution containing 25 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 20 minutes.

[0586] Next, a cyclohexane solution containing 37.5 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 35 minutes.

[0587] Thereafter, methanol was added to terminate the polymerization reaction, thereby obtaining a conjugated diene block copolymer.

[0588] Next, the hydrogenation catalyst prepared above was added to the obtained conjugated diene block copolymer in an amount of 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and a hydrogenation reaction was performed at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.5 hours.

[0589] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate was added as a stabilizer based on 100 parts by mass of the hydrogenated conjugated diene block copolymer.

[0590] The hydrogenated conjugated diene block copolymer obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.1×10 4 , the vinyl bonding content is 35% and the hydrogenation rate is 98%.

[0591] The hydrogenated conjugated diene block copolymer obtained as described above was mixed with maleic anhydride and peroxide (PERHEXA25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length was set to 150 to 210° C. to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (14-M).

[0592] The obtained maleic anhydride-modified hydrogenated-modified conjugated diene block copolymer (14-M) was titrated under the above conditions. The modification rate was 1.1% by mass.

[0593] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (15)>

[0594] The same operation as in the hydrogenated conjugated diene block copolymer (3) was carried out except that 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as "DMI") was added to 1 mol of n-butyl lithium before adding methanol, and the reaction was carried out at 70° C. for 15 minutes. After the reaction, methanol was added.

[0595] The terminal amine-modified conjugated diene block copolymer (15) obtained as described above had a styrene content of 65% by mass and a weight average molecular weight of 18.9×10 4 , the vinyl bond content was 26%, the modification rate was 80% by mass (the number of modified groups per polymer chain was 0.80), and the hydrogenation rate was 82%.

[0596] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (16)>

[0597] A hydrogenated conjugated diene block copolymer (16) was obtained by carrying out the same operation as that of the hydrogenated conjugated diene block copolymer (1) except that the hydrogenation reaction time was changed to 0.75 hours.

[0598] The hydrogenated conjugated diene block copolymer (16) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210°C to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (16)-M.

[0599] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (16)-M was titrated under the above conditions. The modification rate was 0.5% by mass.

[0600] The terminal maleic anhydride-modified conjugated diene block copolymer (16)-M obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.0×10 4, the vinyl bond content is 36% and the hydrogenation rate is 45%.

[0601] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (17)>

[0602] A hydrogenated conjugated diene block copolymer (17) was obtained by carrying out the same operation as that of the hydrogenated conjugated diene block copolymer (1) except that the hydrogenation reaction time was changed to 1 hour.

[0603] The hydrogenated conjugated diene block copolymer (17) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210°C to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (17)-M.

[0604] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (17)-M was titrated under the above conditions. The modification rate was 0.8% by mass.

[0605] The terminal amine-modified conjugated diene block copolymer (17)-M obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bond content is 35% and the hydrogenation rate is 88%.

[0606] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (18)>

[0607] A hydrogenated conjugated diene block copolymer (18) was obtained by carrying out the same operation as that of the hydrogenated conjugated diene block copolymer (3) except that the hydrogenation reaction time was changed to 1 hour.

[0608] The hydrogenated conjugated diene block copolymer (18) obtained as described above is mixed with maleic anhydride and peroxide (PERHEXA 25B, manufactured by NOF Corporation), and then supplied to a twin-screw extruder in which the temperature of the entire region of the extruder length is set to 150 to 210°C to prepare a composite, thereby obtaining a maleic anhydride-modified hydrogenated conjugated diene block copolymer (18)-M.

[0609] The obtained maleic anhydride-modified hydrogenated conjugated diene block copolymer (18)-M was titrated under the above conditions. The modification rate was 0.8% by mass.

[0610] The terminal amine-modified conjugated diene block copolymer (18)-M obtained as described above had a styrene content of 65% by mass and a weight average molecular weight of 18.9×10 4 , the vinyl bond content is 26% and the hydrogenation rate is 82%.

[0611] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (19)>

[0612] Before adding methanol, 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as "DMI") was added to 1 mol of n-butyl lithium, and the reaction was carried out at 70°C for 15 minutes. After the reaction, methanol was added. The same operation as the hydrogenated conjugated diene block copolymer (9) was carried out except that the maleic anhydride modification step was not carried out.

[0613] The terminal amine-modified conjugated diene block copolymer (19) obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bond content was 70%, the modification rate was 80% by mass (the number of modified groups per polymer chain was 0.80), and the hydrogenation rate was 88%.

[0614] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (20)>

[0615] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0616] First, a cyclohexane solution containing 20 parts by mass of butadiene (concentration: 20% by mass) was added.

[0617] Next, 0.068 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.30 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0618] Next, a cyclohexane solution (concentration: 20% by mass) containing 20 parts by mass of styrene and 60 parts by mass of butadiene was added, and polymerization was carried out at 70° C. for 45 minutes.

[0619] Next, 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as “DMI”) was added to 1 mol of n-butyllithium, and the mixture was reacted at 70° C. for 15 minutes.

[0620] Thereafter, methanol was added to terminate the polymerization reaction.

[0621] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.0 hour.

[0622] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (20).

[0623] The hydrogenated conjugated diene block copolymer (20) obtained as described above had a styrene content of 20% by mass and a weight average molecular weight of 15.0×10 4 , the vinyl bond content is 35% and the hydrogenation rate is 85%.

[0624] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (21)>

[0625] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0626] First, a cyclohexane solution (concentration: 20% by mass) containing 10 parts by mass of styrene was added.

[0627] Next, 0.068 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.68 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0628] Next, a cyclohexane solution containing 80 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 45 minutes.

[0629] Next, a cyclohexane solution containing 10 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 15 minutes.

[0630] Next, 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as “DMI”) was added to 1 mol of n-butyllithium, and the mixture was reacted at 70° C. for 15 minutes.

[0631] Thereafter, methanol was added to terminate the polymerization reaction.

[0632] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.0 hour.

[0633] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (21).

[0634] The hydrogenated conjugated diene block copolymer (21) obtained as described above had a styrene content of 20% by mass and a weight average molecular weight of 15.0×10 4 , the vinyl bond content is 55% and the hydrogenation rate is 84%.

[0635] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (22)>

[0636] Batch polymerization was carried out using a tank-type reactor (internal volume 10 L) equipped with a stirring device and a jacket.

[0637] First, a cyclohexane solution (concentration: 20% by mass) containing 15 parts by mass of styrene was added.

[0638] Next, 0.14 parts by mass of n-butyl lithium relative to 100 parts by mass of all monomers and 0.23 mol of tetramethylethylenediamine (TMEDA) relative to 1 mol of n-butyl lithium were added, and polymerization was carried out at 70° C. for 15 minutes.

[0639] Next, a cyclohexane solution containing 70 parts by mass of butadiene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 40 minutes.

[0640] Next, a cyclohexane solution containing 15 parts by mass of styrene (concentration: 20% by mass) was added, and polymerization was carried out at 70° C. for 15 minutes.

[0641] Next, 1.1 mol of 1,3-dimethyl-2-imidazolidinone (hereinafter also referred to as “DMI”) was added to 1 mol of n-butyllithium, and the mixture was reacted at 70° C. for 15 minutes.

[0642] Thereafter, methanol was added to terminate the polymerization reaction.

[0643] Next, the hydrogenation catalyst prepared above was added to the conjugated diene block copolymer obtained above at 70 ppm based on Ti per 100 parts by mass of the conjugated diene block copolymer, and hydrogenation was carried out at a hydrogen pressure of 0.7 MPa and a temperature of 80° C. for about 1.2 hours.

[0644] Next, 0.25 parts by mass of octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate as a stabilizer was added to 100 parts by mass of the hydrogenated conjugated diene block copolymer to obtain a hydrogenated conjugated diene block copolymer (22).

[0645] The hydrogenated conjugated diene block copolymer (22) obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bonding content is 35% and the hydrogenation rate is 94%.

[0646] <Preparation of Hydrogenated Conjugated Diene Block Copolymer (23)>

[0647] The same operation as the hydrogenated conjugated diene block copolymer (22) was carried out except that the hydrogenation reaction time was changed to 1.2 hours. The hydrogenated conjugated diene block copolymer (23) obtained as described above had a styrene content of 30% by mass and a weight average molecular weight of 7.0×10 4 , the vinyl bond content is 35% and the hydrogenation rate is 65%.

[0648] (Manufacture of polypropylene resin composition)

[0649] The conjugated diene copolymers (1) to (23) and (1)-M, (3)-M, (4)-M, (8)-M, (9)-M, (10)-M, (16)-M, (17)-M and (18)-M were mixed with a polypropylene resin (PL500A, manufactured by SunAllomer) to obtain a mixture (polypropylene / conjugated diene copolymer = 80 / 20). The mixture was then supplied to a twin-screw extruder set at a temperature of 150 to 220° C. over the entire length of the extruder, and the obtained strands were cooled and cut into pellets to obtain pellets of a polypropylene resin composition.

[0650] [Manufacturing of Laminated Body (Examples 1 to 40, Comparative Examples 1 to 15)]

[0651] (Manufacturing of Laminated Body (Examples 1 to 18, Comparative Examples 1 to 6))

[0652] A laminate of a three-layer structure of layer (I), layer (II) and layer (III) was produced. First, each of the hydrogenated conjugated diene block copolymers was press-molded at 200° C. to produce a hydrogenated conjugated diene block copolymer sheet (thickness: 0.5 mm).

[0653] Next, the hydrogenated conjugated diene block copolymer sheet was layered between a 2 mm thick flat plate made of acrylic resin (DELPET 80N manufactured by Asahi Kasei Corporation) and a 2 mm thick flat plate made of polypropylene resin (PL500A manufactured by SunAllomer Corporation), and heated and pressed (200° C.) in a mold (thickness 4.5 mm) of the same shape as the above-mentioned flat plates to produce a laminate.

[0654] (Manufacturing of Laminated Body (Examples 19 to 31, Comparative Examples 7 to 12))

[0655] A laminate having a two-layer structure of layer (I) and layer (IV) containing a polyolefin resin and an adhesive component was produced. First, a 2 mm thick flat plate made of acrylic resin was installed in a mold of an injection molding machine, and the cylinder temperature was set at 200° C., and the polypropylene resin composition was injected to produce a laminate.

[0656] (Production of Laminated Body (Examples 32 to 40, Comparative Examples 13 to 15))

[0657] A two-layer film (layer (I) about 30 μm, layer (III) 10 μm) in contact with layer (I) is produced by co-extrusion molding using a multi-layer T-die extruder under the conditions of extrusion temperature (layer (I): 230°C, layer (III): 200°C) and die temperature (230°C).

[0658] Next, the two-layer film was set in a mold (flat plate, temperature 50° C.) of an injection molding machine, the cylinder temperature was set at 200° C., and the polypropylene resin was injected to laminate layer (II) to produce a laminate.

[0659] [Examples 1 to 18], [Comparative Examples 1 to 6]

[0660] The adhesive component was used as a single layer (layer (III)), and a three-layer laminate consisting of the layer (III), layer (I): acrylic resin, and layer (II): polypropylene resin was prepared. The properties of the laminate were evaluated.

[0661] [Examples 19 to 31], [Comparative Examples 7 to 12]

[0662] A two-layer laminate consisting of a polypropylene resin composition layer (layer (IV)) in which an adhesive component and a polypropylene resin are mixed and an acrylic resin layer (layer (I)) was prepared, and the properties of the laminate were evaluated.

[0663] [Examples 32 to 40], [Comparative Examples 13 to 15]

[0664] The adhesive component was used as a single layer (layer (III)), and a three-layer laminate consisting of layer (III), layer (I): acrylic resin 30 μm, and layer (II): polypropylene resin was prepared. The properties of the laminate were evaluated.

[0665] The structures and physical properties of the hydrogenated conjugated diene block copolymers (1) to (23) are shown in Tables 1 to 3 below.

[0666]

[0667] The evaluation results of the properties of the three-layer laminate are shown in Tables 4 and 5 below.

[0668] In Comparative Examples 3 and 4 using the hydrogenated conjugated diene copolymers (8) and (10), the layer (I) and the layer (II) were not bonded together, and a laminate was not obtained.

[0669]

[0670] The evaluation results of the two-layer laminate consisting of a polypropylene resin composition layer (layer (IV)) in which an adhesive component and a polypropylene resin are mixed and an acrylic resin layer (layer (I)) are shown in Tables 6 and 7 below.

[0671] In Comparative Examples 9 and 10 using the hydrogenated conjugated diene copolymers (8) and (10), the layer (I) and the layer (IV) were not bonded together, and a laminate was not obtained.

[0672]

[0673] The evaluation results of a three-layer laminate consisting of a single layer (layer (III)) containing the adhesive component, layer (I): acrylic resin, and layer (II): polypropylene resin are shown in Tables 8 and 9 below.

[0674]

[0675] As can be seen from Examples 1 to 40 and Comparative Examples 1 to 15, the laminate of the present invention is excellent in adhesive strength and appearance.

[0676] This application is based on the Japanese patent application (Japanese Patent Application No. 2022-092456) filed with the Japan Patent Office on June 7, 2022, the contents of which are incorporated into this specification by reference.

[0677] Industrial Applicability

[0678] The laminate of the present invention can achieve both sufficient adhesive strength and appearance, and has industrial applicability as decorative molded bodies such as vehicle parts, electronic devices such as televisions, and containers.

Claims

1. A laminate comprising: A layer (I) mainly composed of acrylic resin; a layer (II) mainly composed of a polyolefin resin; and The adhesive layer (III) provided between the layer mainly composed of acrylic resin and the layer mainly composed of polyolefin resin is: The adhesive layer (III) is composed of an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) having a vinyl aromatic monomer unit and a conjugated diene monomer unit, wherein the unsaturated bonds of the conjugated diene monomer unit are hydrogenated. The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv), <Condition (i)> The hydrogenated conjugated diene block copolymer has a polar group; <Condition (ii)> The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises a unit (a) derived from a 1,2-bond and / or a 3,4-bond of a conjugated diene compound, and a unit (b) derived from a 1,4-bond, and when the total content of the conjugated diene monomer units is 100%, the content of the unit (a) derived from the 1,2-bond and / or the 3,4-bond is 50% or more; <Condition (iii)> The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C); <Condition (iv)> The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less.

2. The laminate according to claim 1, wherein The hydrogenated conjugated diene-based block copolymer satisfies the conditions (i), (iii), and (iv).

3. The laminate according to claim 1, wherein The hydrogenated conjugated diene-based block copolymer satisfies the conditions (ii), (iii), and (iv).

4. The laminate according to claim 1, wherein The hydrogenated conjugated diene block copolymer satisfies the conditions (i) and (ii), does not satisfy the condition (iv), and further satisfies the following condition (v), <Condition(v)> The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene-based block copolymer is less than 25% by mass.

5. The laminate according to claim 1, wherein The hydrogenated conjugated diene block copolymer satisfies the condition (i), and the polar group of the hydrogenated conjugated diene block copolymer is at least one selected from the group consisting of anhydride group, amino group, dicarboxyl group, carboxyl group, epoxy group and oxetanyl group.

6. The laminate according to claim 5, wherein: The polar group of the hydrogenated conjugated diene block copolymer is an amino group.

7. The laminate according to claim 6, wherein: The hydrogenation rate of the hydrogenated conjugated diene block copolymer is 90% or less.

8. The laminate according to claim 1 or 7, wherein: The thickness of the layer (I) mainly composed of acrylic resin is 1.5 mm or less.

9. The laminate according to claim 7, wherein: The hydrogenated conjugated diene-based block copolymer satisfies the condition (iv).

10. A method for producing a laminate, which is the method for producing a laminate according to claim 1, comprising the following steps: A step of laminating the layer (I) mainly composed of acrylic resin and the adhesive layer (III) in such a manner that the layer (I) is in contact with each other; and A step of laminating the layer (II) mainly composed of a polyolefin resin so that the adhesive layer (III) is in contact with the layer (II) mainly composed of a polyolefin resin.

11. The method for producing a laminate according to claim 10, wherein: The thickness of the layer (I) mainly composed of acrylic resin is 1.5 mm or less.

12. The method for producing a laminate according to claim 10, wherein: In the step of laminating the layer (I) mainly composed of an acrylic resin and the adhesive layer (III), the layer (I) mainly composed of an acrylic resin and the adhesive layer (III) are laminated in a molten state.

13. The method for producing a laminate according to claim 10, wherein: In the step of laminating the layer (II) mainly composed of a polyolefin resin, The laminate having the layer (I) mainly composed of the acrylic resin and the adhesive layer (III) is installed in a mold, The polyolefin resin is poured into the mold in a molten state.

14. A laminate comprising: a layer (I) mainly composed of an acrylic resin; and A layer (IV) comprising a polyolefin resin and an adhesive component, wherein The mass ratio of the polyolefin resin to the adhesive component is polyolefin resin / adhesive component=30 / 70 to 95 / 5. The adhesive component is an adhesive component mainly composed of a hydrogenated conjugated diene block copolymer, wherein the hydrogenated conjugated diene block copolymer has two or more polymer blocks selected from the group consisting of a polymer block (A) mainly composed of a vinyl aromatic monomer unit, a polymer block (B) mainly composed of a conjugated diene monomer unit, and a polymer block (C) composed of a vinyl aromatic monomer unit and a conjugated diene monomer unit, wherein the unsaturated bonds of the conjugated diene monomer unit are hydrogenated, The hydrogenated conjugated diene block copolymer satisfies two or more of the following conditions (i) to (iv), <Condition (i)> The hydrogenated conjugated diene block copolymer has a polar group; <Condition (ii)> The conjugated diene block copolymer before hydrogenation of the hydrogenated conjugated diene block copolymer comprises a unit (a) derived from a 1,2-bond and / or a 3,4-bond of a conjugated diene compound, and a unit (b) derived from a 1,4-bond, and when the total content of the conjugated diene monomer units is 100%, the content of the unit (a) derived from the 1,2-bond and / or the 3,4-bond is 50% or more; <Condition (iii)> The hydrogenated conjugated diene-based block copolymer has at least one polymer block (C); <Condition (iv)> The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene block copolymer is 25% by mass or more and 80% by mass or less.

15. The laminate according to claim 14, wherein The hydrogenated conjugated diene-based block copolymer satisfies the conditions (i), (iii), and (iv).

16. The laminate according to claim 14, wherein The hydrogenated conjugated diene-based block copolymer satisfies the conditions (ii), (iii), and (iv).

17. The laminate according to claim 14, wherein The hydrogenated conjugated diene block copolymer satisfies the conditions (i) and (ii), does not satisfy the condition (iv), and further satisfies the following condition (v), <Condition(v)> The content of the vinyl aromatic monomer unit in the hydrogenated conjugated diene-based block copolymer is less than 25% by mass.

18. The laminate according to claim 14, wherein The hydrogenated conjugated diene block copolymer satisfies the condition (i), and the polar group of the hydrogenated conjugated diene block copolymer is at least one selected from the group consisting of anhydride group, amino group, dicarboxyl group, carboxyl group, epoxy group and oxetanyl group.

Citation Information

Patent Citations

  • Structure integrated by vacuum pressure forming or vacuum forming, and manufacturing method thereof

    JP2013014027A

  • Production method of decorative molded article

    JP2021181232A

  • Information processing system and program

    JP2022092456A

  • Composition and surface protective film

    CN106164166A

  • Laminate and its manufacture

    JP1999216810A